Stress distribution Glass-based articles having enhanced stress regions
By performing ion exchange treatment on the lithium-based aluminosilicate glass substrate, products with high compression stress peaks and potassium enrichment areas are formed, which solves the problem of uneven compression stress distribution in existing glass products and improves the product Mechanical and chemical reliability.
Patent Information
- Application Number
- CN202080049289.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-07-02
- Filing Date
- 2020-07-01
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2040-07-01
AI Technical Summary
Existing glass-based products have shortcomings in mechanical and chemical reliability, especially in the issue of uneven compression stress distribution, which leads to prone to rupture during falls or impacts.
By performing ion exchange treatment on a glass substrate of the lithium-based aluminosilicate composition, an article with a specific stress distribution is formed. The article includes forming a high compression stress spike area in the surface area and extending through the potassium enrichment area to the center of the article, ensuring the presence of the reinforced stress area and the potassium enrichment area.
A uniform distribution of high compression stress in glass products is achieved, thereby improving the mechanical and chemical reliability of the products and reducing the risk of rupture during drop or impact.
Smart Images

Figure CN114144385B_ABST
Abstract
Description
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims priority under 35 USC §119 to U.S. Provisional Application Serial No. 62 / 869,887, filed on July 2, 2019, which is hereby relied upon and incorporated herein by reference in its entirety. Technical Field
[0003] Embodiments of the present disclosure generally relate to glass-based articles having improved stress distribution and methods of making the same. Background Art
[0004] Glass-based products are used in many various industries, including consumer electronics, transportation, construction, protection, medical and packaging. For consumer electronics, glass-based products are used in electronic devices as covers or windows for portable or mobile electronic communication and entertainment devices, such as mobile phones, smart phones, tablets, watches, video players, information terminals (IT) devices, laptops, and navigation systems. In construction, glass-based products are included in windows, shower panels and countertops; and in transportation, glass-based products are present in vehicles, trains, aircraft and marine vehicles. Glass-based products are suitable for any application that would benefit from excellent shatter resistance but thin and lightweight products. For each industry, the mechanical and / or chemical reliability of glass-based products is generally driven by function, performance and cost. Improving the mechanical and / or chemical reliability of these products is a continuous goal.
[0005] Chemical treatment is a strengthening method that imparts a desired and / or engineered stress profile having one or more of the following parameters: compressive stress (CS), depth of compression (DOC), and maximum central tension (CT). Many glass-based articles, including those having an engineered stress profile, have compressive stress that is highest or peaked at the surface of the glass and decreases from the peak as it moves away from the surface, and is zero stress at some location inside the glass article before the stress in the glass article becomes tensile. Chemical strengthening by ion exchange (IOX) of alkali-containing glasses is a proven method in the art.
[0006] In the consumer electronics industry, chemically strengthened glass is used as the material of choice for display covers due to its improved aesthetic appearance and scratch resistance compared to plastic, as well as better drop performance and better scratch resistance compared to non-strengthened glass.
[0007] For these industries, there is a continuing need for glass-based articles that are mechanically and / or chemically reliable. There is also a continuing need to achieve this in a cost-effective manner. Summary of the invention
[0008] Aspects of the present disclosure pertain to glass-based articles and methods of making them.
[0009] The first aspect is a glass-based article comprising: a lithium-based aluminosilicate composition; a glass-based substrate having first and second opposing surfaces defining a substrate thickness (t), wherein t is less than or equal to 0.74 mm; and a stress profile comprising: a maximum compressive stress (CS) greater than or equal to 450 MPa. max ); a peak region extending from the first surface to the tail region; and a tail region extending to the center of the glass-based article; wherein the tail region comprises: a first average compressive stress (CS avg-1 ) greater than or equal to 100 MPa of the enhanced stress region; and a FSM layer depth (DOL) located at a depth greater than or equal to 13 microns FSM ).
[0010] Another aspect is a glass-based article comprising: a lithium-based aluminosilicate composition; a glass-based substrate having opposing first and second surfaces defining a substrate thickness (t), wherein t is less than or equal to 0.74 mm; and a stress profile comprising: a maximum compressive stress (CS) greater than or equal to 450 MPa. max ); extending from the first surface to the peak layer depth (DOL sp ) peak area; and from DOL sp A tail region extending to the center of the glass-based article; wherein the tail region includes: sp Add 1 micron to the depth of potassium layer (DOL K ) of a potassium-enriched region having a second average compressive stress (CS) greater than or equal to 100 MPa. avg-2 ), among which, DOL k Located at a depth greater than or equal to 20 microns.
[0011] Another aspect is a glass-based article comprising: a lithium-based aluminosilicate composition, wherein the molar ratio of Na2O:Li2O in the lithium-based aluminosilicate composition is greater than or equal to 1; a glass-based substrate having first and second opposing surfaces defining a substrate thickness (t), wherein t is greater than or equal to 0.2 mm and less than or equal to 0.74 mm; and a stress profile comprising: a maximum compressive stress (CS) greater than or equal to 450 MPa. max ); Maximum central tension (CT) greater than or equal to 40MPa max ); a peak region extending from the first surface to the tail region; and a tail region extending to the center of the glass-based article; wherein the tail region comprises: a first average compressive stress (CS avg-1) greater than or equal to 100 MPa of the enhanced stress region; and a FSM layer depth (DOL) located at a depth greater than or equal to 13 microns FSM ).
[0012] Another aspect is a glass-based article comprising: a lithium-based aluminosilicate composition; a glass-based substrate having opposing first and second surfaces defining a substrate thickness (t), wherein t is greater than or equal to 0.2 mm and less than or equal to 0.74 mm; and a non-zero concentration of potassium oxide (KO) from the first surface to a depth of potassium layer (DOL). K ) is varied; and a stress distribution comprising: a maximum compressive stress (CS) greater than or equal to 450 MPa max ); Maximum central tension (CT) greater than or equal to 40MPa max ); extending from the first surface to the peak layer depth (DOL sp ) peak area; and from DOL sp A tail region extending to the center of the glass-based article; wherein the tail region includes: sp Add 1 micron extension to DOL K A potassium-enriched region having a second average compressive stress (CS) greater than or equal to 100 MPa and less than or equal to 170 MPa avg-2 ), among which, DOL k Located at a depth greater than or equal to 20 microns.
[0013] Other aspects provide a consumer electronic product comprising: a housing having a front surface, a back surface, and side surfaces; electronic components at least partially located within the housing, the electronic components comprising at least a controller, a memory, and a display, the display being located on the front surface of the housing or adjacent to the front surface of the housing; and a cover arranged above the display, wherein at least a portion of at least one of the housing and the cover comprises a glass-based article of any embodiment of the present invention.
[0014] Another aspect is a method of making a glass-based article, comprising: exposing a glass-based substrate comprising sodium oxide and lithium oxide in a base composition to an ion exchange treatment to form a glass-based article, the glass-based substrate having opposing first and second surfaces defining a substrate thickness (t), the ion exchange treatment comprising: a first bath comprising potassium salt, sodium salt and lithium salt; and a second bath comprising potassium salt, sodium salt and optionally lithium salt; wherein t is less than or equal to 0.74 mm and the substrate comprises a composition wherein the molar ratio of Na2O:Li2O in the lithium-based aluminosilicate composition is greater than or equal to 1; wherein the glass-based article comprises a stress profile comprising: a maximum compressive stress (CS) greater than or equal to 450 MPa; max); extending from the first surface to the peak layer depth (DOL sp ) peak area; and from DOL sp A tail region extending to the center of the glass-based article; wherein the tail region includes: sp Add 1 micron to the depth of potassium layer (DOL K ) of a potassium-enriched region having a second average compressive stress (CS) greater than or equal to 100 MPa. avg-2 ), among which, DOL K Located at a depth greater than or equal to 20 microns. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate several embodiments described below.
[0016] Figure 1A schematically shows a cross section of glass having a compressive stress layer on its surface according to embodiments disclosed and described herein;
[0017] Figure 1B Provides an excerpt of a representative RNF-generated stress profile for half the thickness of an article according to some embodiments disclosed herein (67 hour first step) and a representative comparative example curve "A" showing a comparative example stress profile without the first K-enrichment step;
[0018] Figure 2A is a plan view of an exemplary electronic device incorporating any of the glass-based articles disclosed herein;
[0019] Figure 2B yes Figure 2A A perspective view of an exemplary electronic device;
[0020] Figure 3 is the FSM layer depth (DOL) for two different second IOX step bath compositions according to some embodiments disclosed herein. FSM ) versus the first 10X step time (hours);
[0021] Figure 4 is the recorded FSM stress (CS) for two different second IOX step bath compositions according to some embodiments disclosed herein. max ) versus the first 10X step time (hours);
[0022] Figure 5 is a graph of SCALP central tension (CT) versus first IOX step time (hours) for two different second IOX step bath compositions according to some embodiments disclosed herein;
[0023] Figure 6 is the FSM layer depth (DOL) for two different second IOX step bath compositions and the same third IOX step according to some embodiments disclosed herein. FSM ) versus the first 10X step time (hours);
[0024] Figure 7 is the recorded FSM stress (CS) for two different second IOX step bath compositions and the same third IOX step according to some embodiments disclosed herein. max ) versus the first 10X step time (hours);
[0025] Figure 8 is a graph of SCALP central tension (CT) versus first IOX step time (hours) for two different second IOX step bath compositions and the same third IOX step according to some embodiments disclosed herein;
[0026] Fig. 9 is the FSM layer depth (DOL) for the second IOX step bath and the third IOX step according to some embodiments disclosed herein. FSM ) versus the first 10X step time (hours);
[0027] Fig.10 is the recorded FSM stress (CS) for the second IOX step bath and the third IOX step according to some embodiments disclosed herein max ) versus the first 10X step time (hours);
[0028] Fig.11 is a graph of SCALP central tension (CT) versus first IOX step time (hours) for the second IOX step bath and the third IOX step according to some embodiments disclosed herein;
[0029] Fig.12 is the FSM layer depth (DOL) for the second IOX step bath and the third IOX step according to some embodiments disclosed herein. FSM ) versus the first 10X step time (hours);
[0030] Fig.13 is the recorded FSM stress (CS) for the second IOX step bath and the third IOX step according to some embodiments disclosed herein max ) versus the first 10X step time (hours);
[0031] Fig.14is a graph of SCALP central tension (CT) versus first IOX step time (hours) for the second IOX step bath and the third IOX step according to some embodiments disclosed herein;
[0032] Fig.15 is the FSM layer depth (DOL) of the second 10X step bath for three different durations according to some embodiments disclosed herein. FSM ) versus the first 10X step time (hours);
[0033] Fig.16 is the recorded FSM stress (CS) for the second 10X step bath for three different durations according to some embodiments disclosed herein. max ) versus the first 10X step time (hours);
[0034] Fig.17 is a graph of SCALP central tension (CT) versus first IOX step time (hours) for three different durations of the second IOX step bath according to some embodiments disclosed herein;
[0035] Fig.18 is the FSM layer depth (DOL) of the second 10X step bath for three different durations according to some embodiments disclosed herein. FSM ) versus the first 10X step time (hours);
[0036] Fig.19 is the recorded FSM stress (CS) for the second 10X step bath for three different durations according to some embodiments disclosed herein max ) versus the first 10X step time (hours);
[0037] Fig. 20 is a graph of SCALP central tension (CT) versus first IOX step time (hours) for three different durations of the second IOX step bath according to some embodiments disclosed herein;
[0038] Fig.21 is a graph of SCALP central tension (CT) versus first IOX step time (hours) for a second IOX step bath according to some embodiments disclosed herein;
[0039] Fig. 22 is the FSM layer depth (DOL) for the second IOX step bath and different third IOX steps according to some embodiments disclosed herein. FSM ) versus the first 10X step time (hours);
[0040] Fig.23is the recorded FSM stress (CS) for the second IOX step bath and a different third IOX step according to some embodiments disclosed herein max ) versus the first 10X step time (hours);
[0041] Fig.24 is a graph of SCALP central tension (CT) versus first IOX step time (hours) for a second IOX step bath and different third IOX steps according to some embodiments disclosed herein;
[0042] Fig.25A and 25B is a stress distribution diagram according to some embodiments disclosed herein, Fig.25A The stress (MPa) versus depth up to half the thickness of the part is plotted, and Fig.25B This is the case up to a product depth of 110 microns;
[0043] Fig.26A and 26B is a stress distribution diagram according to some embodiments disclosed herein, Fig.26A The stress (MPa) versus depth up to half the thickness of the part is plotted, and Fig.26B This is the case up to a depth of 110 microns;
[0044] Fig. 27 is a graph of stress distribution (MPa) versus depth up to half thickness according to some embodiments disclosed herein;
[0045] Fig.28 is a graph of stress distribution (MPa) versus depth up to half thickness according to some embodiments disclosed herein;
[0046] Fig.29 is a plot of depth of compression (DOC) versus time (hours) of the first IOX step, and the sample was subjected to three IOX steps;
[0047] Fig.30 is the stress profile (MPa) of stress versus depth up to half thickness according to some embodiments disclosed herein; and
[0048] Fig.31 yes Fig.30 TM and TE refractive index profiles of the stress distribution.
[0049] The accompanying drawings are included to provide a further understanding of the principles described herein, and are incorporated in and constitute a part of this specification. The accompanying drawings illustrate embodiments and, together with the description, serve to explain the principles and operations of those embodiments by way of example. It should be understood that the various features disclosed in this specification and the accompanying drawings may be used in any and all combinations.
[0050] The embodiments described herein and features of those embodiments are exemplary and may be provided alone or in any combination with any one or more features of other embodiments provided herein without departing from the scope of the present disclosure. In addition, it is to be understood that the foregoing general description and the following detailed description present embodiments of the present disclosure to provide an overall review or framework for understanding the nature and characteristics of the embodiments described and claimed. The included drawings provide a further understanding of the embodiments, and the drawings are incorporated into and constitute a part of this specification. The drawings illustrate various embodiments of the present disclosure and are used together with the description to explain its principles and operation.
[0051] In this article, exemplary embodiments that disclose specific details are given for the purpose of illustration rather than limitation to provide a full understanding of various principles and aspects. However, it is obvious to those of ordinary skill in the art that, after benefiting from the present disclosure, the claimed subject matter can be implemented in other embodiments than those described in detail herein. In addition, descriptions of well-known devices, methods, and materials may be omitted to avoid confusing the description of the various principles herein. Finally, the same reference numerals represent the same elements wherever applicable. DETAILED DESCRIPTION
[0052] Before describing several exemplary embodiments, it is to be understood that the present disclosure is not limited to the details of construction or process steps described in the following disclosure. The present disclosure provided herein is capable of other embodiments being practiced or carried out in various ways.
[0053] "One embodiment", "certain embodiments", "various embodiments", "one or more embodiments", or "an embodiment" mentioned throughout this specification means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment are included in at least one embodiment of the present disclosure. Therefore, phrases such as "in one or more embodiments", "in certain embodiments", "in various embodiments", "in one embodiment", or "in an embodiment" appearing in various places throughout this specification do not necessarily refer to the same embodiment. In addition, specific features, structures, materials, or characteristics may be combined in one or more embodiments in any suitable manner.
[0054] Definition and measurement techniques
[0055] The terms "glass-based article" and "glass-based substrate" are used to include any object made in whole or in part of glass (including glass-ceramics, which contain amorphous phases and crystalline phases). Laminated glass-based articles include laminates of glass and non-glass materials, for example, laminates of glass and crystalline materials. According to one or more embodiments, the glass-based substrate can be selected from: alkali aluminosilicate glass, alkali-containing borosilicate glass, alkali-containing aluminoborosilicate glass, and alkali-containing phosphosilicate glass.
[0056] The "base composition" is the chemical makeup of the substrate prior to any ion exchange (IOX) treatment. That is, the base composition is not doped with any ions from the IOX. When the IOX treatment conditions are such that the ions supplied by the IOX do not diffuse into the center of the substrate, the composition at the center of the IOX-treated glass-based article is generally the same as the base composition. In one or more embodiments, the composition at the center of the glass article comprises the base composition.
[0057] Reference to "chemical balance" means that any diffusion of two or more alkali ions of the base composition of the substrate or the core composition of the article into the IOX bath is less than about 10%.
[0058] It is noted that the terms "substantially" and "approximately" may be used herein to represent the degree of inherent uncertainty that may result from any quantitative comparison, value, measurement, or other representation. These terms are also used herein to represent that a stated value of a quantity may deviate from a stated reference value to a certain extent without resulting in a change in the basic function of the subject matter under consideration. Thus, for example, a glass-based article that is substantially free of "MgO" is a glass-based article in which MgO is not actively added or compounded into the glass-based article, but may be present in very small amounts (e.g., less than 0.01 mole %) as a contaminant. As used herein, the term "about" indicates that amounts, dimensions, formulations, parameters, and other variables and characteristics are not and need not be exact, but may be approximate and / or larger or smaller as desired, reflecting tolerances, conversion factors, rounding and measurement errors, etc., and other factors known to those skilled in the art. When the term "about" is used to describe a value or end-point of a range, it should be understood that the present disclosure includes the specific value or end-point referenced. Regardless of whether or not the value or endpoint of a range in this specification states "about", the value or endpoint of the range is intended to include two embodiments: one modified by "about" and one not modified by "about". For example, "about 10 mol %" is intended to disclose a value modified by about as well as an exact value of 10 mol %. It will also be understood that the endpoints of each range are significant both in relation to the other endpoint and independently of the other endpoint.
[0059] As used herein, the terms "substantially," "substantially," and variations thereof are intended to mean that the described features and values or descriptions are equal or approximately the same. For example, a "substantially planar" surface is intended to mean a planar or approximately planar surface. Additionally, "substantially" is intended to mean that two values are equal or approximately equal. In some embodiments, "substantially" can mean that values are within about 10% of each other, such as within about 5% of each other, or within about 2% of each other.
[0060] Unless otherwise stated, all compositions described herein are expressed in mole percent (mol %) on an oxide basis.
[0061] "Stress profile" is stress relative to the location of a glass-based article or any portion thereof. A compressive stress region extends from a first surface of the article to a depth of compression (DOC) where the article is under compressive stress. A central tension region extends from the DOC to include a region of the article that is under tensile stress.
[0062] As used herein, depth of compression (DOC) refers to the depth at which stress within a glass-based article changes from compressive to tensile stress. At the DOC, stress changes from positive (compressive) stress to negative (tensile) stress, thereby exhibiting a zero stress value. According to common practice in the mechanical field, compression is expressed as negative stress (<0) and tension is expressed as positive stress (>0). However, throughout this specification, compressive stress (CS) is expressed as a positive or absolute value, that is, CS=|CS| stated herein. When used with the term "tensile", stress or central tension (CT) can be expressed as a positive value, that is, CT=|CT|. Central tension (CT) refers to the tensile stress in the central area or central tension area of a glass-based article. Maximum central tension (maximum CT or CT max ) exists in a central tension region nominally at 0.5t, where t is the article thickness, allowing for variations in the actual center relative to the location of the maximum tensile stress. Peak tension (PT) refers to the maximum tension measured, which may or may not be located at the center of the article.
[0063] The "inflection point" of stress distribution is a relatively sudden transition from a steep slope to a gentle slope. The depth of this transition can be called the "inflection point depth" or simply the "inflection point". Inflection point stress (CS 拐点 ) is the stress at the point where the slope of the stress distribution transitions from steep to gentle. CS can be determined from the stress distribution measured by the refracted near field (RNF) 拐点 For the stress profile with the compressive stress-enhanced region disclosed herein (which is discussed in the inventive examples herein), CS 拐点It is also possible to measure the stress distribution in a non-destructive manner from a part by using prism coupling and using the inverse WKB method (see Figure 30-31 The optical mode spectra (TM and TE) are measured using a 2D scatter plot (discussed in the literature) and statistically smoothed to remove artifacts associated with the stepwise linear aspect of the inverse WKB pathway. The CS value at the depth of highest curvature of the smoothed distribution near the inflection point can be taken as the CS 拐点 This is the CS value on the gradient branch of the CS curve, where the slope of the distribution begins to increase rapidly as the depth decreases toward the surface. The depth at this location on the gradient branch is usually equal to DOL sp Or slightly higher than DOL sp (Up to 20% or 1-2 microns higher). Expected CS 拐点 The CS value will be between this value and a value up to 20 MPa higher. For the comparative example Li-based glass that was ion exchanged in a Na-containing bath without the strengthening of the present disclosure, the CS can be measured non-destructively by RNF stress distribution measurement or by using the birefringence of the critical angle transition measured in prism coupling. 拐点 In one or more embodiments, after exposure to two or more ion exchange treatment steps (K enrichment step and at least one secondary IOX), the stress profile includes potassium enriched regions that are compressive stress strengthened regions. References to "enrichment" or "strengthening" are with respect to glasses that have not been exposed to the K enrichment step. Thus, it is possible to report CS ranges for strengthened compressive stress regions and / or potassium enriched regions. The average compressive stress for each type of region can also be calculated. The average compressive stress in a region (e.g., CS in a strengthened stress region) is the average compressive stress in the region. avg-1 and / or CS in potassium-rich areas avg-2 ) will convey such distribution characteristics. In addition, CS can be recorded 拐点 The value of CS is used to characterize the strengthening stress. 拐点 There may be uncertainties of up to 20 MPa related to measurement accuracy limits.
[0064] A non-zero metal oxide concentration that varies from a first surface to a depth of layer (DOL) relative to the metal oxide, or that varies at least along a majority of the article thickness (t), indicates that stress has been created in the article as a result of ion exchange. The change in metal oxide concentration may be referred to herein as a metal oxide concentration gradient. A metal oxide that has a non-zero concentration and varies from a first surface to a DOL, or varies along a portion of the thickness, may be described as creating stress in a glass-based article. A concentration gradient or change in metal oxide is created by chemically strengthening a glass-based substrate, wherein a plurality of first metal ions in the glass-based substrate are exchanged with a plurality of second metal ions.
[0065] As used herein, the terms "exchange depth," "depth of layer" (DOL), "chemical depth of layer," and "depth of chemical layer" are used interchangeably and generally describe the depth of ion exchange driven by an ion exchange process (IOX) for a particular ion. The DOL refers to the depth within a glass-based article (i.e., the distance from the surface of the glass-based article to an interior region thereof) at which ions of a metal oxide or alkali oxide (e.g., a metal ion or an alkali ion) diffuse into the glass-based article where the concentration of the ion reaches a minimum or reaches a value substantially similar to that in an extruded glass composition, as determined by glow discharge-optical emission spectroscopy (GD-OES). In some embodiments, the DOL is given as the exchange depth of the slowest diffusing ion or the largest ion introduced by the ion exchange (IOX) process. The DOL relative to potassium (DOL k ) is the depth at which the potassium content of the glass article reaches the potassium content of the underlying substrate. In some embodiments, DOL can be determined by measuring the depth of the TE and TM refractive index profiles via inverse WKB (IWKB) of the measured prism-coupled spectra. K (This article refers to Figure 30-31 Since IWKB only extracts the refractive index distribution up to the depth (turning point) of the deepest detected boundary mode, it is preferred to use the deeper end point of the TE and TM refractive index distributions as the DOL. K The peak layer depth (DOL) at the bottom of the compressive stress peak can be determined by statistically smoothing the stress distribution measured by the refracted near field (RNF). sp For stress profiles with compressive stress-enhanced regions as disclosed herein (discussed in the inventive embodiments herein), the peak is a region of high CS and high CS slope extending from the surface to approximately the inflection point depth. The depth of the peak (DOL) is measured using a modified prism coupling technique. sp ), thereby taking into account the presence of a more densely discrete spectrum of CS-enhanced regions and their associated optical modes. sp The value of can be obtained by a formula relating the depth of a linear refractive index profile to the number of boundary optical modes supported by the profile, which is provided in conjunction with the embodiments herein.
[0066] As used herein, DOL FSM Refers to the DOL result measured using an FSM prism coupler with standard FSM-6000 software, which calculates the DOL based on the formula for the depth of linear refractive index profile mentioned above. The RNF stress distribution can be statistically smoothed to account for measurement variations. DOL FSM Based on the number / spectrum of fringes based on measuring potassium concentration.FSM The results are based on the assumption that there is a linear potassium concentration in the tail region after the spike. The distribution of the present invention does not have a linear potassium concentration in the region after the spike, but rather there is an enhanced potassium region. As a result, DOL FSM With DOL K are different.
[0067] Unless otherwise indicated, CT and CS are expressed herein in megapascals (MPa), thickness is expressed in millimeters (mm), and DOC and DOL are expressed in micrometers (micrometers or μm).
[0068] Compressive stress (including surface and / or peak CS, CS max ). Surface stress measurements rely on accurate measurement of the stress-optical coefficient (SOC), which is related to the birefringence of the glass. SOC is measured according to Protocol C (Glass Disc Method) described in ASTM Standard C770-16, entitled "Standard Test Method for Measurement of Glass Stress-Optical Coefficient", which is incorporated herein by reference in its entirety.
[0069] The maximum central tension (CT, CT) was measured using the scattered light polariscope (SCALP) technique known in the art. max ) or peak tension (PT, PT max ) and stress retention value. The stress distribution and compression depth (DOC) can be measured using the refracted near field (RNF) method or SCALP. When the RNF method is used to measure the stress distribution, the maximum CT value provided by SCALP is used in the RNF method. Specifically, the stress distribution measured by RNF is force balanced and calibrated with the maximum CT value provided by the SCALP measurement. The RNF method is described in U.S. Patent No. 8,854,623, entitled "Systems and methods for measuring a profile characteristic of a glass sample", which is incorporated herein by reference in its entirety.
[0070] Overview of properties of glass-based products
[0071] The present disclosure relates to chemically strengthened cover glasses, and more particularly, to lithium-containing chemically strengthened cover glasses and glass-based articles. Throughout the present disclosure, when referring to "glass," it should be recognized that the same concepts apply to glass-based articles. For a given surface compressive stress (CS max ), increase the depth of compression (DOC) and / or the inflection stress CS 拐点 Helps reduce the possibility of breakage during drops onto rough surfaces. While lithium-based glasses achieve high DOC via rapid sodium (Na) diffusion and high CS via shallow potassium (K) diffusion max , but generally speaking, in the case of high CS max and a sufficiently deep DOL sp or DOL K The peak and high inflection point stress CS 拐点 There is a trade-off between CS max and CS 拐点 No such tradeoff exists in Na-based glasses where independent control is performed.
[0072] When the cover glass sheet has a small thickness (for example, less than or equal to 0.6 mm, but in particular less than or equal to 0.55 mm and greater than or equal to 0.05 mm), CS 拐点 With CS max / DOL sp The tradeoff between DOC and OC can be problematic. In such low thickness applications, increasing the DOC can provide a modest benefit, but in practice, it is difficult to increase the DOC to thicknesses above about 20% when a distinct spike is also desired. Therefore, in such cases, increasing the inflection point stress becomes the primary way to reduce the likelihood of cracking during a drop on a rough surface. Specifically, in 3D shaped cover glasses, it is most common that the curved portion of the cover glass tends to contact the rough surface and there is significant stress during the contact event. Generally speaking, cracks in such cases arise from defects that are not particularly deep (e.g., defects in the range of 20-50 microns rather than 60-200 microns), but that experience higher tensile stress levels (typically levels in excess of 100 MPa) during a drop event. It would be advantageous to provide a region of enhanced compressive stress (particularly potassium enriched). The enhanced stress region can be located at least 100 m from the DOL. sp (or slightly deeper, such as DOL sp plus 1 micron) extends to the FSM layer depth (DOL) FSM ) depth, with the first average compressive stress (CS avg-1In one or more embodiments, the enhanced stress region is at a depth of greater than or equal to 8 microns to less than or equal to 45 microns, including greater than or equal to 10 microns to less than or equal to 40 microns, and all values and subranges therebetween. The potassium-enriched region can be defined as: from DOL sp (or slightly deeper, such as DOL sp plus 1 micron) extends to the depth of potassium layer (DOL) K ), with a second average compressive stress (CS avg-2 In one or more embodiments, the potassium-enriched zone is at a depth of greater than or equal to 10 microns to less than or equal to 75 microns, including greater than or equal to 20 microns to less than or equal to 50 microns, and all values and subranges therebetween.
[0073] Commonly assigned U.S. Patent Application Publication 2020 / 0002225 improves stress distribution by using K enrichment, such as having increased CS 拐点 0.8mm glass.
[0074] The stress distribution resulting from the methods and articles herein improves the directional drop breakage resistance on 3D shaped 0.5 mm thick cover glass for next generation cell phones.
[0075] The examples herein differ from those of US2020 / 0002225 in the following respects:
[0076] (1) This disclosure focuses on thin glass, with examples having a thickness of 0.5 mm instead of 0.8 mm. Low CS at 0.5 mm 拐点 The problem is even more problematic, which increases the significance of the compressive stress increase in the 10 micron and deeper regions.
[0077] (2) The K enrichment method of the present disclosure is different from US2020 / 0002225. In US2020 / 0002225, the weight ratio of Li:Na is the same as that in a K-free bath, which is balanced with a glass of the following composition: 63.60 mol% SiO2, 15.67 mol% Al2O3, 10.81 mol% Na2O, 6.24 mol% Li2O, 1.16 mol% ZnO, 0.04 mol% SnO2 and 2.48 mol% P2O5. More specifically, the weight ratio of LiNO3 / NaNO3 in the bath is 0.205. In contrast, in this article, the weight ratio of LiNO3 / NaNO3 is increased in the presence of a significant amount of KNO3 in the bath (thereby producing an extended region of compressive stress immediately following the surface spike). Otherwise, the glass substrate will be enriched with Na during the K enrichment step, resulting in a less desirable final distribution (with lower CT and CS) after the subsequent step of chemical strengthening.拐点 ), the subsequent step introduces a deep Na profile and helps provide a large DOC, which is a major benefit of Li-containing glasses. In the examples of the present disclosure, when KNO3 accounts for 30 wt% of the potassium enrichment first step bath, an increased LiNO3 / NaNO3 weight ratio of 0.273 is used to avoid Na enrichment of the glass during the K enrichment step. This LiNO3:NaNO3 ratio is significantly higher than the equilibrium ratio of the KNO3-free bath used in US2020 / 0002225, and it is advantageous to use this higher ratio, thereby obtaining the benefits of K enrichment without paying the price of reducing the total integrated stress (which is estimated by the associated CT drop). Compared to US2020 / 0002225, the present disclosure uses a different mixing weight ratio of 30% KNO3:55% NaNO3:15% LiNO3 for the potassium enrichment partial equilibrium bath. The term "partially balanced" is used to indicate that the bath is substantially balanced for Li-Na ion exchange with the glass, but is not balanced for K-Na and K-Li exchange.
[0078] (3) The present disclosure provides examples of penetration of a significantly wider range of deep K-enriched layers. Examples include K-enrichment to depths of 13 microns, 27 microns, 36 microns, 51 microns, and 60-76 microns. These examples more fully cover the problematic depth range of interest of 20-50 microns for improving crack resistance as determined by directional drop tests using three molded 0.5 mm thick cover glass test devices on rough granite. Note that for thinner substrates (e.g., 0.2-0.6 mm, 0.5 mm is exemplified in the present disclosure), additional penetration of K-enrichment is advantageous (significantly beyond the target depth of boosting CS) because K-enrichment tends to reduce compression of stress distribution at depths comparable to and above the K-enriched regions. For example, K enrichment to a depth of 27 microns is advantageous, thereby achieving a net advancement of CS in a distribution up to a depth of less than or equal to 20 microns, compared to a reference distribution without a K enrichment step; K enrichment to a depth of 36 microns is advantageous for the advancement of CS in a region extending up to about 25 microns. Similarly, K enrichment to 51 microns is advantageous, providing CS benefits up to a depth of 30 microns. Finally, K enrichment to a depth of more than 60 microns is advantageous, providing a net gain of CS up to a depth of about 40 microns, compared to a reference distribution without K enrichment. It is apparent that the K enrichment depth can typically be 1.2 to 2 times higher than the target depth of CS advancement, and this multiple increases with the increase in the target depth of advancing CS. The examples of US2020 / 0002225 cover a narrower range of K enrichment depths (20 to 30 microns), which would provide a limited CS advancement depth if applied to a thinner substrate (e.g., 0.5 mm). This K enrichment depth range also exhibits small values of ratio of thickness t (0.025t to 0.0375t). The present disclosure covers K penetration up to about 76 microns (or 0.15t). As the K enrichment depth as a ratio of thickness increases, it becomes even more advantageous to avoid Na enrichment of the substrate during the K enrichment step.
[0079] (4) The present disclosure demonstrates a different approach to verifying that the bath composition for potassium enrichment is partially balanced (e.g., such that the Na:Li ratio in the glass does not substantially change during the potassium enrichment step). This approach is based on anchoring a narrow range of weight gain for the potassium enrichment step and is cheaper and more convenient to perform. Furthermore, it is less prone to errors (e.g., errors arising from inaccurate calibration of the instrument for chemical analysis).
[0080] (5) Avoiding Na enrichment in the first step by adopting a favorable bath composition and a low-cost robust validation process helps prevent the bath composition from drifting from a non-equilibrium initial composition toward an equilibrium composition as the glass article is produced. Such a drift can result in differences in final product parameters between parts made using the bath at different stages of such a drift cycle, which can lead to yield problems.
[0081] (6) Some examples have higher CS (over 1000 MPa) and even over 1050 MPa or 1100 MPa, while having high CS 拐点 . This type of very high CS and high CS 拐点 The combination did not exist before and will become extremely valuable in the future, especially for thinner 3D formed cover glass products.
[0082] The present disclosure proposes a stress profile of a zone with increased compressive stress (strengthened CS) that exists in a depth region from about 8 to about 80 microns, where the upper end of this zone may drop to 70, 60, 50, 40, 30, 25, 20, or 15 microns, depending on the tradeoff between the amount of mechanical strength benefit and the increased cost of the process steps performed (e.g., increased ion exchange time). The strengthened CS region is typically arranged between the surface peak and this deep region, where the potassium level of the deep region is equal to the baseline potassium level at the midpoint thickness of the glass sheet. Another tradeoff is the depth of the strengthened CS region and the DOC, which may drop when the depth of the strengthened CS region is too large.
[0083] The strengthened CS region may contain CS values above 100 MPa, above 110 MPa, 120 MPa, 130 MPa, 140 MPa, 150 MPa, and up to 350 MPa and all ranges therebetween. In some cases, the strengthened CS region may contain CS above 200 MPa and contain potassium and sodium both significantly above the baseline level inside the substrate. In some cases, there is a tradeoff between how high the CS strengthening is and how much the DOC drops as a result of such CS strengthening in the strengthened CS region.
[0084] Strengthening the CS region helps prevent situations where the depth of defects formed during a drop onto a rough surface is less than the depth of the strengthened CS region, and where the cover glass is subjected to significant bending resulting in cracking when the tips of these defects are subjected to significant tension if the strengthened stress profile does not provide sufficient compressive stress to prevent tension and cracking. It may also be the case that, in some cases, strengthening the CS region helps reduce the likelihood of deep defects forming or reduce the depth of defects that are formed.
[0085] In addition to the region of strengthened CS, the present stress profile also has a high compression depth (typical of prior art stress profiles for Li-containing glasses), a central tension preferably above 40 MPa, 45 MPa, 50 MPa, 55 MPa, 60 MPa, or 65 MPa, and may preferably have a surface peak of compressive stress with a maximum compressive stress above 450 MPa, 500 MPa, 550 MPa, 600 MPa, 650 MPa, or 700 MPa. In some examples, the maximum compressive stress in the peak may be above 800 MPa, and even above 1000 MPa, 1050 MPa, or 1100 MPa.
[0086] In some embodiments, the strengthened CS region is formed in part by a potassium enrichment ion exchange step in a bath having a mixture of potassium salt, sodium salt and lithium salt, and the glass product is a Li-containing glass. In the potassium enrichment step, the glass product is substantially free of Na enrichment. Specifically, it may be balanced with the ion exchange bath relative to the ion exchange between Na and Li ions. This keeps the composition of the interior of the glass substantially unchanged during the formation of the potassium enriched layer. In some embodiments, very slight Na enrichment may be acceptable as part of normal variations in production conditions. In some embodiments, slightly purposeful or unpurposeful Li enrichment may be used to advance the total stress of the final stress distribution. Control of the correct use of the bath composition can be effectively achieved by measuring the weight change of the glass sample after the potassium enrichment step or measuring the growth of the glass sheet. In both cases, the target is a small change in weight or size, mainly corresponding to the amount of K exchanged into the glass to replace Na and Li, without a significant contribution of Na to exchange Li. If the final stress is desired to be pushed by a slightly targeted Li enrichment that occurs during the potassium enrichment step, the LiNO3:NaNO3 weight ratio in the bath can be increased up to 50% by replacing NaNO3 with LiNO3 and keeping KNO3 constant or increasing KNO3 slightly (again at the expense of NaNO3). In addition, the bath will benefit from periodic replenishment of the LiNO3 enriched salt mixture to keep the bath from deviating from equilibrium so that the target Li enrichment of the glass is maintained from run to run.
[0087] In some embodiments, high peak CS, high CS 拐点 and high DOC, which is usually unattainable in thin Li-based glass substrates via ion exchange with Na providing high DOC and K providing high peak CS. Such a combination can be used to mitigate some failure modes, such as cracking that introduces damage combined with significant stress, which is dominant in some cases (e.g., thin (0.3-0.6 mm) 3D formed cover glasses).
[0088] See also Figure 1A , the glass has a thickness t and a first region under compressive stress (e.g., Figure 1A The first and second compressive stress layers 120, 122 in the embodiment of the present invention and the second region (e.g., Figure 1A The first region extends from the surface to the depth of compression (DOC) of the glass, and the second region extends from the DOC into the center or inner region of the glass.
[0089] The compressive stress (CS) has a maximum or peak value, which is usually present at the surface of the glass (but this is not necessarily the case, as the peak value can be present at a depth from the surface of the glass), and the CS varies as a function of the distance d relative to the surface. Referring again to FIG. 1 , the first compressive stress layer 120 extends from the first surface 110 to a depth d1, and the second compressive stress layer 122 extends from the second surface 112 to a depth d2. Together, these segments define the compression or CS of the glass 100.
[0090] Two compressive stress layers ( Figure 1A The compressive stresses in the glass (120, 122) are balanced by the tension stored in the central region (130) of the glass.
[0091] Figure 1B is an excerpt of an exemplary, non-limiting, RNF-generated stress profile (67 hour first step) for half the thickness of an article according to some embodiments disclosed herein, and a representative comparative example curve "A" showing the comparative example stress profile in the absence of the first K enrichment step. For this 67 hour first step stress profile and other stress profiles, depths up to half the article thickness are illustrated herein, with the understanding that the stress profile is symmetrical. When a double-sided IOX treatment scheme and uniform substrate composition are employed, the stress profile is generally considered to be symmetrical. The stress profile contains: a peak region near the surface that extends to an inflection point; and a tail region extending deeper into the glass from the inflection point toward the center. The stress profile includes: a maximum compressive stress (CS max ); Layer depth (DOL) measured by FSM FSM ); Depth of peak layer (DOL sp ), inflection stress (CS 拐点 ), depth of compression (DOC) (this is where the stress in the glass first becomes zero and changes sign from compression to tension), and central tension (CT or CT max ) (This is the stress at the center of the glass). The depth of potassium layer (DOL) can be determined as discussed above K ).exist Figure 1B For illustrative purposes, compressive stress is assumed to be positive and tensile stress is assumed to be negative. The peak region extends from the surface to the DOLsp , and the tail area from DOL sp The enhanced stress region is located in the tail region, and the enhanced stress region is enhanced relative to the stress profile "A" of the comparative example without the K enrichment step. In addition, the potassium-enriched region is also located in the tail region, and the potassium-enriched region is enriched relative to the stress profile "A" of the comparative example without the K enrichment step. sp Add 1 micron to DOL FSM The average compressive stress in the depth (CS avg-1 ), will provide a way to characterize the enhanced stress region. It is important to understand that DOL FSM falls within the enhanced stress region, but may not necessarily be exactly at the boundary of this region. It is also important to understand that DOL sp may not necessarily be exactly the boundary of this region, so for calculation purposes, CS avg-1 From DOL sp Add 1 micron to DOL FSM . sp Add 1 micron to DOL K The average compressive stress in the depth (CS avg-2 ), will provide a means of characterizing potassium-rich regions. It is to be understood that DOL K falls within the potassium-rich region, but may not necessarily be exactly on the border of this region. It is also important to understand that DOL sp may not necessarily be exactly the boundary of this region, so for calculation purposes, CS avg-2 From DOL sp Add 1 micron to DOL K All points in the peak region of the stress distribution include the tangent with an absolute value of slope of 20 MPa / micrometer or more, and the stress distribution is located at a point greater than DOL K All points in the deep tail region include tangents with absolute values of slopes less than 20 MPa / micrometer.
[0092] Disclosed herein are lithium (Li) glass-based articles of thickness t having an improved stress profile with an enhanced stress region in a subsurface inflection region.
[0093] Specifically, the favorable stress distribution of the thin Li-containing glass article has a strengthened stress region having a first average compressive stress (CS) greater than or equal to 100 MPa. avg-1 ) and the FSM layer depth (DOL) located at a depth greater than or equal to 13 microns FSM ) combined with one or any combination of the following: CS maxGreater than or equal to 450 MPa, including: greater than or equal to 500 MPa, greater than or equal to 550 MPa, greater than or equal to 600 MPa, greater than or equal to 650 MPa, and greater than or equal to 700 MPa, wherein t is greater than or equal to 0.2 mm and / or less than or equal to 0.74 mm, including all values and ranges therebetween, including: less than or equal to 0.65 mm, less than or equal to 0.6 mm, less than or equal to 0.5 mm, less than or equal to 0.4 mm, and less than or equal to 0.3 mm.
[0094] In one or more embodiments, the glass-based article comprises: a FSM layer depth (DOL) greater than or equal to 13 microns to less than or equal to 55 microns. FSM ), including all values and subranges therebetween, for example: greater than or equal to 15 microns to less than or equal to 50 microns, or greater than or equal to 20 microns to less than or equal to 45 microns, or greater than or equal to 22 microns to less than or equal to 40 microns, or greater than or equal to 25 microns to less than or equal to 35 microns.
[0095] In one or more embodiments, the glass-based article comprises a DOL greater than or equal to 3 microns and less than or equal to 20 microns. sp , including all values and subranges therebetween, for example: greater than or equal to 5 microns to less than or equal to 19 microns, greater than or equal to 6 microns to less than or equal to 12 microns, greater than or equal to 6.2 microns to less than or equal to 8 microns, greater than or equal to 10.5 microns to less than or equal to 15 microns, or greater than or equal to 11 microns to less than or equal to 15 microns, or greater than or equal to 8 microns to less than or equal to 15 microns, or greater than or equal to 8.5 microns to less than or equal to 14.5 microns, or greater than or equal to 9 microns to less than or equal to 14 microns, or greater than or equal to 9.5 microns to less than or equal to 13.5 microns, or greater than or equal to 10 microns to less than or equal to 13 microns, or greater than or equal to 10.5 microns to less than or equal to 12.5 microns, or greater than or equal to 11 microns to less than or equal to 12 microns.
[0096] In one or more embodiments, the glass-based article comprises a DOL greater than or equal to 20 microns and less than or equal to 75 microns. K , including all values and subranges therebetween, for example: greater than or equal to 22 microns to less than or equal to 70 microns, or greater than or equal to 25 microns to less than or equal to 65 microns, or greater than or equal to 30 microns to less than or equal to 60 microns, or greater than or equal to 35 microns to less than or equal to 55 microns, or greater than or equal to 40 microns to less than or equal to 50 microns.
[0097] In one or more embodiments, the glass-based article comprises an average compressive stress (CSavg-1 ) is a strengthened stress region greater than or equal to 100 MPa and / or less than or equal to 220 MPa (and all values and subranges therebetween). In one or more embodiments, the glass-based article comprises an average compressive stress (CS avg-2 ) is a potassium-rich region greater than or equal to 100 MPa and / or less than or equal to 170 MPa (and all values and subranges therebetween).
[0098] In one or more embodiments, the glass-based article comprises: an inflection point compressive stress (CS) greater than or equal to 160 MPa and / or less than or equal to 300 MPa. 拐点 ), and all values and subranges therebetween, including greater than or equal to 165 MPa and / or less than or equal to 295 MPa.
[0099] In one or more embodiments, the glass-based article comprises: a maximum central tension (CT) greater than or equal to 40 MPa and / or less than or equal to a value of 3 / √t MPa. max ), where t is measured in millimeters, and all values and subranges therebetween.
[0100] In one or more embodiments, the glass-based article comprises a depth of compression (DOC) greater than or equal to 0.12 t and / or less than or equal to 0.25 t, and all values and subranges therebetween.
[0101] The stress distribution may include: a peak region extending from the first surface to a tail region; and a tail region extending to the center of the glass-based article; wherein all points in the stress distribution located in the peak region include a tangent having an absolute value of a slope of 20 MPa / micrometer or greater, and all points in the stress distribution located in the tail region include a tangent having an absolute value of a slope less than an absolute value of a slope of the tangent of the peak region.
[0102] In the glass-based article, there is a metal oxide having a non-zero concentration that varies from a first surface to a depth of layer (DOL) relative to the metal oxide. In one or more embodiments, the metal oxide having a non-zero concentration that varies from the first surface is potassium, having a DOL K. The stress distribution is generated due to the non-zero concentration of the metal oxide that varies starting from the first surface. The non-zero concentration can vary along a portion of the thickness of the article. In some embodiments, the concentration of the metal oxide is non-zero and varies along a thickness range from 0t to about 0.3t. In some embodiments, the concentration of the metal oxide (e.g., potassium) is non-zero and varies along the following thickness range: 0t to about 0.050t, or 0t to about 0.0.25t, or 0t to about 0.020t, or 0t to about 0.0175t, or 0t to about 0.015t, or 0t to about 0.0125t, or 0t to about 0.010t. In some embodiments, the change in concentration may be continuous along the above thickness range. The change in concentration can include from the surface to the DOL (e.g., DOL K ) varies by at least about 0.2 mol %. In some embodiments, the metal oxide concentration from the surface to the DOL (e.g., DOL K ), the metal oxide concentration change can be at least about 0.3 mol%, or at least about 0.4 mol%, or at least about 0.5 mol%. This change can be measured by methods known in the art (including microprobes).
[0103] In some embodiments, the concentration variation can be continuous along a thickness segment of about 10 microns to about 30 microns. In some embodiments, the concentration of the metal oxide decreases from the first surface to a value at a point between the first surface and the second surface, and increases from the value to the second surface.
[0104] The concentration of metal oxides may include more than one metal oxide (e.g., a combination of Na2O and KO). In some embodiments, when two metal oxides are used and when the ionic radii are different from each other, at shallow depths, the concentration of ions with larger radii is greater than the concentration of ions with smaller radii, while at greater depths, the concentration of ions with smaller radii is greater than the concentration of ions with larger radii. For example, when a single bath containing Na and K is used in the ion exchange process, at shallow depths, the concentration of K in the glass-based article is greater than the concentration of K in the glass-based article. + The concentration of ions is greater than that of Na + ion concentration, while at greater depths, Na + The concentration of ions is greater than K + This is due, at least in part, to the size of the monovalent ions that are exchanged with smaller monovalent ions into the glass. In such glass-based articles, the presence of larger ions (e.g., K +ions), the region at or near the surface includes a larger CS. In addition, the slope of the stress distribution generally decreases with distance from the surface due to the characteristics of the concentration distribution achieved by chemical diffusion from a fixed surface concentration.
[0105] In one or more embodiments, the metal oxide concentration gradient extends through a majority of the article thickness t. In some embodiments, the concentration of the metal oxide may be about 0.5 mol % or greater (e.g., about 1 mol % or greater) along the entire thickness of the first and / or second segments, and be maximum at the first surface and / or the second surface Ot, and decrease substantially constantly to a value at a point between the first surface and the second surface. At this point, the concentration of the metal oxide is the lowest along the entire thickness t; however, the concentration may also be non-zero at this point. In other words, the non-zero concentration of the particular metal oxide extends along a majority of the thickness t (as described herein) or along the entire thickness t. The total concentration of the particular metal oxide in the glass-based article may be about 1 mol % to about 20 mol %.
[0106] The concentration of the metal oxide can be determined by the baseline amount of the metal oxide in the glass-based substrate that is ion exchanged to form the glass-based article.
[0107] In one or more embodiments, all points of the stress distribution located in the peak region include a tangent having an absolute value of a slope of 20 MPa / micrometer or greater.
[0108] In one or more embodiments, the glass-based article comprises a maximum compressive stress (CS) greater than or equal to 450 MPa. max , nominally at the first surface). For example, CS max Greater than or equal to 450 MPa and less than or equal to 1700 MPa, greater than or equal to 500 MPa to less than or equal to 1600 MPa, greater than or equal to 550 MPa to less than or equal to 1400 MPa, greater than or equal to 600 MPa to less than or equal to 1200 MPa, greater than or equal to 650 MPa to less than or equal to 1000 MPa, greater than or equal to 700 MPa to less than or equal to 950 MPa, greater than or equal to 700 MPa to less than or equal to 900 MPa, greater than or equal to 700 MPa to less than or equal to 850 MPa, greater than or equal to 700 MPa to less than or equal to 800 MPa, or about 750 MPa, and all values and subranges therebetween.
[0109] In one or more embodiments, the glass-based article comprises a thickness of greater than or equal to 0.02 mm to less than or equal to 0.74 mm, including all values and ranges therebetween, including less than or equal to 0.65 mm, less than or equal to 0.6 mm, less than or equal to 0.5 mm, less than or equal to 0.4 mm, and less than or equal to 0.3 mm.
[0110] In one or more embodiments, the glass-based article comprises a base composition having a Na2O:Li2O molar ratio greater than or equal to 1 and less than or equal to 1.8, for example: greater than or equal to 1.4, or greater than or equal to 1.5, or greater than or equal to 1.6 and / or less than or equal to 1.7, including all values and subranges therebetween, including 1, 1.14, 1.56 and 1.69.
[0111] Glass-based substrates
[0112] Examples of glasses that can be used as substrates can include alkali aluminosilicate glass compositions or alkali aluminoborosilicate glass compositions, but other glass compositions are also contemplated. Such glass compositions can be characterized as ion exchangeable. As used herein, "ion exchangeable" means that the substrate comprises a composition that enables the exchange of cations of the same valence, either larger or smaller in size, with cations located at or near the surface of the substrate.
[0113] In some embodiments, the substrate may include a lithium-containing alkali aluminosilicate glass. In some embodiments, the lithium-containing alkali aluminosilicate glass has a composition, in mol%, comprising: SiO2 in an amount of about 60% to about 75%, Al2O3 in an amount of about 12% to about 20%, B2O3 in an amount of about 0% to about 5%, Li2O in an amount of about 2% to about 8%, Na2O in an amount greater than about 4%, MgO in an amount of about 0% to about 5%, ZnO in an amount of about 0% to about 3%, CaO in an amount of about 0% to about 5%, and P2O5 in a non-zero amount, wherein the glass substrate is ion-exchangeable and amorphous, wherein the total amount of Al2O3 and Na2O in the composition is greater than about 15 mol%. In one or more embodiments, the amount of Na2O is greater than or equal to 4% and less than or equal to 12%.
[0114] In embodiments, the glass-based substrate may be formed from any composition capable of forming the described stress profile. In some embodiments, the glass-based substrate may be formed from the glass compositions described in U.S. Application No. 16 / 202,691, filed on November 28, 2018, entitled “Glasses with Low Excess Modifier Content,” which is incorporated herein by reference in its entirety. In some embodiments, the glass article may be formed from the glass compositions described in U.S. Application No. 16 / 202,767, filed on November 28, 2018, entitled “Ion-Exchangeable Mixed Alkali Aluminosilicate Glasses,” which is incorporated herein by reference in its entirety.
[0115] The glass-based substrate may be characterized by the manner in which it is formed. For example, the glass-based substrate may be characterized as float-formable (i.e., formed by a float process), down-drawable, specifically, fusion-formable, or slot-drawable (i.e., formed by a down-draw process such as a fusion-draw process or a slot-draw process). In embodiments, the glass-based substrate may be roll-formed.
[0116] The glass-based substrate prepared by floating molten glass on a bed of molten metal (usually tin) to produce float glass is characterized by a smooth surface and uniform thickness. In an exemplary process, molten glass is fed onto the surface of a molten tin bed to form a floating glass ribbon. As the glass ribbon flows along the tin bath, the temperature gradually decreases until the glass ribbon solidifies into a solid glass-based substrate, which can be lifted from the tin onto rollers. Once out of the bath, the glass-based substrate can be further cooled, annealed to reduce internal stresses, and optionally polished.
[0117] Some embodiments of the glass-based substrates described herein can be formed by a down-draw process. The down-draw process produces a glass-based substrate having a uniform thickness with a relatively pristine surface. Because the average flexural strength of the glass article is controlled by the amount and size of surface imperfections, the pristine surface with minimal contact has a higher initial strength. The down-drawn glass-based substrate can be drawn to a thickness of less than about 2 mm. In addition, the down-drawn glass article has a very flat, smooth surface that can be used in the final application without costly grinding and polishing.
[0118] Some embodiments of glass-based articles can be described as fusion-formable (i.e., can be formed using a fusion drawing process). The fusion process uses a drawing tank having a channel for receiving molten glass raw materials. The channel has a weir that is open at the top of both sides of the channel along the length of the channel. When the channel is filled with molten material, the molten glass overflows from the weir. Under the action of gravity, the molten glass flows down from the outer surface of the drawing tank as two flowing glass films. The outer surfaces of these drawing tanks extend downward and inward so that they join at the edge below the drawing tank. The two flowing glass films join at this edge and fuse and form a single flowing glass product, which includes a fusion line that can be detected by a microscope at or near the center of the product. The advantage of the fusion drawing method is that since the two glass films overflowing from the channel are fused together, none of the outer surfaces of the resulting glass product is in contact with any part of the equipment. Therefore, the surface properties of the fusion-drawn glass product are not affected by such contact.
[0119] Some embodiments of the glass-based substrates described herein can be formed by a slot draw process. The slot draw process is different from the fusion draw method. In the slot draw process, molten raw material glass is provided to a drawing tank. The bottom of the drawing tank has an open slot with a nozzle extending along the length of the slot. The molten glass flows through the slot and / or nozzle, and is drawn down as a continuous product and enters an annealing zone.
[0120] Ion Exchange (IOX) Treatment
[0121] Chemical strengthening of a glass substrate having a basic composition is accomplished by placing an ion-exchangeable glass substrate in a solution containing cations (K + 、Na + 、Ag + In a molten bath of + 、Na + 、Ag + At the same time, the smaller alkaline ions (Na + , Li + ) diffuse out into the molten bath. The replacement of smaller ones with larger cations creates compressive stresses near the top surface of the glass. Tensile stresses are created in the interior of the glass, balancing the compressive stresses.
[0122] For the ion exchange process, they can independently be a thermal diffusion process or an electrodiffusion process. Other additional strengthening treatments can be selected from the group consisting of ion exchange, thermal annealing, thermal tempering, and combinations thereof.
[0123] After the ion exchange process is performed, it is understood that the composition at the surface of the glass-based article may be different from the composition of the as-formed glass-based substrate (i.e., the glass-based object before it was subjected to the ion exchange process). This is due to the fact that one type of alkali metal ion (e.g., Li + Or Na + ) are replaced by larger alkali metal ions (e.g., Na + or K + However, in embodiments, the composition at or near the depth center of the glass-based article will still have the composition of the as-formed glass-based substrate.
[0124] In one or more embodiments, a partially balanced bath is used for potassium enrichment. The partially balanced bath for potassium enrichment has the following properties: it provides potassium ions to the glass to exchange Na and Li ions, but does not exceed the molar concentration of Na2O and Li2O that changes the depth of the potassium enrichment layer. This means that there is no net exchange of Na ions and Li ions between the bath and the glass, so the bath can be considered to be balanced with respect to Na-Li exchange, but unbalanced for K-Na and K-Li exchange. The bath can be considered to be partially balanced with the glass, and the ion exchange process can be called partially balanced. Because it is partially balanced, the partially balanced bath has a process cost advantage. The bath has a substantially unlimited life because it only loses potassium ions due to ion exchange and loses salt volume due to dragging out (salts taken out of the bath due to adhesion to the glass surface and the device that immerses the glass in the bath). In most cases, these losses can be restored to the target volume of the bath by adding KNO3 to the bath. If the KNO3 content of the bath becomes a little too high and slightly interferes with the partial balance of the Li-Na exchange, the ion exchange brings the bath back to equilibrium. Thus, the bath composition is self-correcting, which makes this bath preferred when reducing manufacturing complexity and cost is preferred.
[0125] Some embodiments include a process for enriching a near-surface layer of a glass-based article with potassium ions (K) by using a first bath, wherein the potassium salt in the first bath is KNO3, present in an amount greater than or equal to 30% by weight, the sodium salt is NaNO3, and the lithium salt is LiNO3. In addition, the weight ratio of LiNO3:NaNO3 in the first bath can be adjusted based on the glass composition. For a glass having a base composition of a molar ratio of Na2O:Li2O of 1.69, the preferred weight ratio of LiNO3:NaNO3 in the first bath is 0.273 or 0.273±0.1%. For a glass having a base composition of a molar ratio of Na2O:Li2O of 1.14, the preferred weight ratio of LiNO3:NaNO3 in the first bath is 0.68 or 0.38±0.1%. For a glass having a base composition of a molar ratio of Na2O:Li2O of 1, the preferred weight ratio of LiNO3:NaNO3 in the first bath is 0.858±0.1%.
[0126] In some examples, it is preferred that the bath is not partially equilibrated, but that the glass is enriched in Li while a K-enriched layer is formed near the surface. In this case, the glass is subjected to a weight gain that is lower than that specified by a partially equilibrated process. Enriching the glass in Li enables a higher level of compressive stress to be obtained at a depth beyond the K-enriched layer during a later step of chemical strengthening, which involves diffusion of Na into the glass. In addition, in this way, a higher central tension can be obtained as an indication of a higher compressive stress integral over the compressive stress layer. Such Li and K enrichment process steps may be forced to result in a weight loss, where a lower weight gain is a negative weight gain. The salts that obtain such enrichment via ion exchange are selected in such a way that the weight change of the article remains within the desired range after such ion exchange, indicating that only potassium ions are exchanged into the article (because if there is a significant sodium (Na) enrichment of the average chemical composition of the article at the expense of lithium (Li), a significant weight gain would be expected; and if there is a significant Li enrichment of the average chemical composition of the article at the expense of Na, a significant weight loss would be expected), where t is the thickness of the article or substrate in mm. Preferably, the preferred weight gain is less than or equal to about 0.1 (1 + 0.02 / t)%, where t is measured in millimeters, including less than or equal to about 0.05 (1 + 0.02 / t)%, or even 0%. The preferred weight loss is less than or equal to 0.3%, 0.25%, 0.21% or even 0.20%. Using the convention that weight loss is negative weight gain, in one or more embodiments, the weight gain value of the glass-based substrate is greater than or equal to -0.3% (or -0.25%, -0.21%, or -0.20%) to less than or equal to 0.1 (1 + 0.02 / t)%, where t is measured in millimeters.
[0127] Some embodiments include using a specific mixture of salts, including, for example, a K-enriched nitrate mixture containing KNO3, LiNO3, and NaNO3, for achieving K enrichment of glass products, such that the Na:Li ratio within the glass interior (e.g., at a depth greater than about 0.010t) has limited or no change. An exemplary K-enriched composition for lithium-based glass is: 55 wt% NaNO3, 15 wt% LiNO3, and 30 wt% KNO3, which is advantageously used for glass substrates having a base composition Na2O:Li2O molar ratio less than or equal to 1.7 or greater than 1, but is not limited thereto.
[0128] In one or more embodiments, a method of making a glass-based article comprises: exposing a glass-based substrate comprising sodium oxide and lithium oxide in a base composition to an ion exchange treatment to form a glass-based article, the glass-based substrate having opposing first and second surfaces defining a substrate thickness (t), the ion exchange treatment comprising: a first bath comprising potassium salt, sodium salt and lithium salt; and a second bath comprising potassium salt, sodium salt and optionally lithium salt; wherein t is less than or equal to 0.74 mm and the substrate comprises a composition wherein the molar ratio of Na2O:Li2O in the lithium-based aluminosilicate composition is greater than or equal to 1; wherein the glass-based article comprises a stress profile comprising: a maximum compressive stress (CS) greater than or equal to 450 MPa; max ); extending from the first surface to the peak layer depth (DOL sp ) peak area; and from DOL sp A tail region extending to the center of the glass-based article; wherein the tail region includes: sp Add 1 micron to the depth of potassium layer (DOL K ) of a potassium-enriched region having a second average compressive stress (CS) greater than or equal to 100 MPa. avg-2 ), among which, DOL KLocated at a depth of greater than or equal to 20 microns. In an embodiment, in the first bath, the potassium salt is KNO3, present in an amount greater than or equal to 30 wt %; the sodium salt is NaNO3; the lithium salt is LiNO3; and the weight ratio of LiNO3:NaNO3 in the first bath is 0.273±0.1%. In an embodiment, after exposure to the first bath, the glass-based substrate has an absolute weight gain of less than or equal to 0.1 (1+0.02 / t), where t is measured in millimeters. In an embodiment, the ion exchange treatment further includes a third bath comprising a potassium salt and a sodium salt, wherein the potassium salt content in the third bath is greater than or equal to 90 wt %. In an embodiment, the first bath comprises: 20-60 wt % NaNO3, 10-20 wt % LiNO3 and 25-60 wt % KNO3, wherein the content of NaNO3, LiNO3 and KNO3 totals 100%, and the glass substrate comprises a base composition having a molar ratio of Na2O:Li2O greater than or equal to 1. In a specific embodiment, the first bath comprises: 50-60 wt% NaNO3, 10-20 wt% LiNO3, and 25-35 wt% KNO3, wherein the contents of NaNO3, LiNO3, and KNO3 total 100%, and the glass substrate comprises a base composition having a molar ratio of Na2O:Li2O greater than or equal to 1.3. In another specific embodiment, the first bath comprises: 20-30 wt% NaNO3, 10-20 wt% LiNO3, and 55-60 wt% KNO3, wherein the contents of NaNO3, LiNO3, and KNO3 total 100%, and the glass substrate comprises a base composition having a molar ratio of Na2O:Li2O greater than or equal to 1 and less than or equal to 1.3.
[0129] Final Product
[0130] The glass-based articles disclosed herein can be integrated into another article, such as an article with a display (or display article) (e.g., consumer electronics, including mobile phones, tablets, computers, watches, and navigation systems, etc.), an architectural article, a transportation article (e.g., a vehicle, a train, an aircraft, a marine vehicle, etc.), an electrical article, or any article that can benefit from partial transparency, scratch resistance, abrasion resistance, or a combination thereof. Figure 2A and 2B Specifically, Figure 2A and 2BA consumer electronic device 200 is shown, comprising: a housing 202 having a front surface 204, a back surface 206, and side surfaces 208; an electronic assembly (not shown) at least partially or completely within the housing and including at least a controller, a memory, and a display 210 located at or adjacent to the front surface of the housing; and a cover plate 212 located at or above the front surface of the housing so that it is located above the display. In some embodiments, at least a portion of the cover plate 212 can include any of the glass-based articles disclosed herein. In some embodiments, at least a portion of the housing 202 can include any of the glass-based articles disclosed herein.
[0131] Example
[0132] Various embodiments are further illustrated by the following examples. In the examples, before being strengthened, the examples are referred to as "substrates". After being strengthened, the examples are referred to as "articles" or "glass-based articles".
[0133] The examples are based on the following compositions: The substrate using composition B in these examples was 0.5 mm thick by 50 mm by 50 mm.
[0134] Composition B is a lithium-based glass-based substrate having the following basic composition: 64.13 mol% SiO2, 15.98 mol% Al2O3, 10.86 mol% Na2O, 0.03 mol% K2O, 6.42 mol% Li2O, 0.08 mol% MgO, 1.17 mol% ZnO, 0.04 mol% SnO2, 1.24 mol% P2O5, and 0.02 mol% CaO. The Na2O:Li2O molar ratio of the basic composition is 1.69, which is greater than 1.0, for example: greater than or equal to 1.1, or greater than or equal to 1.2, or greater than or equal to 1.3.
[0135] Composition C is a lithium-based glass-based substrate having the following base composition: 63.7 mol% SiO2, 16.18 mol% Al2O3, 0.39 mol% B2O3, 2.64 mol% P2O5, 8.04 mol% Li2O, 8.1 mol% Na2O, 0.33 mol% MgO, 0.53 mol% K2O, and 0.05 mol% SnO2. The Na2O:Li2O molar ratio of the base composition is 1.
[0136] Composition D is a lithium-based glass-based substrate having the following base composition: 58.66 mol% SiO2, 17.85 mol% Al2O3, 4.22 mol% B2O3, 1.47 mol% P2O5, 7.67 mol% Li2O, 8.72 mol% Na2O, 1.19 mol% MgO, 0.1 mol% TiO2, 0.07 mol% K2O, and 0.04 mol% SnO2. The Na2O:Li2O molar ratio of the base composition is 1.14.
[0137] The central tension (CT) was measured by scatter polarimetry using a SCALP-5 from Glasstress, Estonia.
[0138] In the following, the recorded FSM stress (CS) is measured by the Orihara FSM-6000LE. max )" and "FSMDOL(DOL FSM )”. The FSM measurement allows the maximum CS (CS max ), and CS decreases monotonically with depth, so the maximum CS at the surface can be measured from the mode spectrum using prism coupling. Record CS at 590nm wavelength max . Then, the recorded FSM maximum CS is given by:
[0139]
[0140] The surface refractive index n of the transverse magnetic (TM) and transverse electric (TE) polarization states is obtained from the positions of the first two fringes in the TM and TE mode spectra measured by prism coupling. TM surf and n TE surf . FSM software uses:
[0141] and
[0142]
[0143] This represents a good approximation for the general case when there may be significant effects of stress relaxation and / or post-immersion diffusion.
[0144] Afterwards, the reference surface stress (CS 表面 ), by changing the FSM software with different coefficients, it is possible to accurately approximate a linear profile from the surface to the second mode depth (the transition point of the second mode) for glasses ion-exchanged below 400 °C (negligible stress relaxation) and for glasses cooled after rapid ion-exchange (e.g., avoiding significant post-immersion diffusion). In this case, the CS maxThe following variation of the equation is used to calculate CS 表面 , where “(lin)” refers to the linear approximation:
[0145]
[0146]
[0147] For the inventive embodiments herein, DOL is obtained by the following equation: sp The value of:
[0148]
[0149] Where λ is the measurement wavelength, N is the fringe count at the measured polarization, n is approximately the average refractive index in the middle of the measured spectrum, and Δn is the refractive index increment between the surface (maximum) refractive index and the lowest refractive index in the assumed refractive index profile. It is usually acceptable to assume that the average refractive index n is equal to the base glass refractive index.
[0150] CS 拐点 For the embodiments of the invention herein, CS is measured in a non-destructive manner from the partial stress distribution. 拐点 , by using prism coupling and the inverse WKB method (ref. Figure 30-31 The optical mode spectra (TM and TE) were measured by statistical smoothing to remove artifacts associated with the stepwise linear aspect of the inverse WKB pathway. The CS value at the depth of highest curvature of the smoothed distribution near the inflection point was taken as CS 拐点 This is the CS value on the gradient branch of the CS curve, where the slope of the distribution begins to increase rapidly as the depth decreases toward the surface. The depth at this location is usually equal to DOL sp Or slightly higher than DOL sp (Up to 20% or 1-2 microns higher). Expected CS 拐点 The CS value is between this value and a value up to 20 MPa higher. For comparative example Li-based glasses that were ion exchanged in a Na-containing bath without strengthening according to the present disclosure, the CS was measured non-destructively by RNF stress profile measurement or by birefringence using critical angle transition measured in prism coupling. 拐点 .
[0151] CS avg-1 and CS avg-2 For the embodiments of this article, the RNF distribution (compressive stress and depth relationship) sampled every 0.25 microns or the IWKB (compressive stress and depth relationship) distribution sampled every 0.2 microns is used to calculate the relationship between the DOL and the RNF distribution. sp Add 1 micron to DOL FSMThe average value of all the sampled compressive stress points is used to obtain CS avg-1 For the embodiments herein, the RNF distribution (compressive stress versus depth relationship) sampled every 0.25 microns or the IWKB (compressive stress versus depth relationship) distribution sampled every 0.2 microns is used to calculate the relationship between the DOL sp Add 1 micron to DOL K The average value of all the sampled compressive stress points is used to obtain CS avg-2 .
[0152] Preparation process
[0153] The process of producing an improved stress distribution including a strengthened stress region comprises one or more of the following steps. The glass substrate sample has a composition B and the following dimensions: thickness 0.5 mm by 50 mm by 50 mm. The composition of the mixed salt bath: potassium nitrate (KNO3), sodium nitrate (NaNO3) and lithium nitrate (LiNO3). Unless otherwise expressly stated, the salt bath concentrations of all the following salt mixtures are specified as weight percent.
[0154] The first ion exchange (IOX) step, which is the K enrichment step, is performed in a double-sided ion exchange in a bath composed of 30% KNO3, 15% LiNO3, and 55% NaNO3. Before starting the first IOX step, the samples were cleaned in deionized water (DI), wiped clean with acetone, and weighed with a high-precision balance. Different samples were ion exchanged in the first step bath at 420°C for different time points, including: 1.5, 8, 15, 30, and 67 hours as recorded, and then characterized individually. Prior to placement in the salt bath, the samples were preheated for 10 to 15 minutes to approach the ion exchange temperature. Cleaning after the first IOX step consisted of thoroughly rinsing the samples with deionized water to remove any residual salts, and then wiping clean with a cloth soaked in acetone.
[0155] Characterization after the first 10X step includes weight gain measurements using a high-precision balance and prismatic coupled stress measurements using the FSM 6000 to determine the compressive stress (CS), inflection stress (CS 拐点 ) and DOL FSM .
[0156] The second ion exchange (IOX) step was a double-sided ion exchange in a bath composed of 49% NaNO3 / 51% KNO3 or 36% NaNO3 / 64% KNO3 at 380°C for various time points, including 1.25, 1.5, or 1.92 hours as recorded. The samples were preheated in an oven for a short time to ensure that there were no distribution changes during the second IOX step. Cleaning after the second IOX step consisted of thoroughly rinsing the samples with deionized water to remove any residual salts, followed by wiping clean with a cloth soaked in acetone.
[0157] As shown below, the second IOX step bath of 49% NaNO3 / 51% KNO3 showed better results than the 36% NaNO3 / 64% KNO3 bath, which led to further research on the second IOX step bath of 49% NaNO3 / 51% KNO3. Additional samples were subjected to the second IOX step bath of 49% NaNO3 / 51% KNO3 at the same temperature of 380°C at two different time points. The additional 1.25 hour second IOX step bath had multiple time points (having been subjected to the first IOX step of the bath being 30% KNO3, 15% LiNO3 and 55% NaNO3), 8 hours, 15 hours and 67 hours. The additional 1.92 hour second IOX step bath had multiple time points (having been subjected to the first IOX step of the bath being 30% KNO3, 15% LiNO3 and 55% NaNO3), 8 hours, 15 hours, 30 hours and 67 hours. All time points through the first and second IOX steps also included a final third IOX step at 370° C. with a bath of 9% NaNO 3 / 91% KNO 3 for 15 minutes, and all conditions were identical in the following paragraphs.
[0158] Characterization after the second IOX step includes weight gain measurement using a high-precision balance, SCALP to measure the central tension (CT), and prismatic coupled stress measurement using the FSM 6000 to determine the compressive stress (CS), inflection stress (CS 拐点 ) and DOL FSM The depth of compression (DOC) of the samples after the second IOX step of 1.25 hours and 1.92 hours with a bath of 49% NaNO3 / 51% KNO3 was calculated by SCALP technique using a SLP-1000 instrument.
[0159] The third ion exchange (IOX) step was a double-sided ion exchange in a bath consisting of either 9% NaNO3 / 91% KNO3 at 370°C for 15 minutes or 100% KNO3 at 380°C for 12 minutes, as recorded. The samples that went through the 49% NaNO3 / 51% KNO3 and 36% NaNO3 / 64% KNO3 baths as the second IOX step also went through the final third IOX step. The samples were preheated briefly in an oven to ensure that there were no distribution changes during the final step. Cleaning after the third step ion exchange consisted of thoroughly rinsing the samples with deionized water to remove any residual salts, then wiping them clean with a cloth soaked in acetone.
[0160] Characterization after the third IOX step includes weight gain measurement using a high-precision balance, SCALP to measure central tension (CT), refractive near field (RNF) to measure birefringence and stress distribution, and prism coupled stress measurement using FSM 6000 to determine compressive stress (CS), inflection stress (CS 拐点 ) and DOL FSM The depth of compression (DOC) was calculated for samples that had undergone a 36% NaNO3 / 64% KNO3 second step bath, a 49% NaNO3 / 51% KNO3 bath in step 2 at two time points at 1.25 hours and 1.92 hours, and then all of these same samples were subjected to a final step of 9% NaNO3 / 91% KNO3 using the SLP-1000 instrument. These measurements were used to determine the overall stress distribution and mechanical properties of each sample.
[0161] The Na, K and Li mentioned in the data tables are ratios, wherein the salts used are nitrates and the amounts are by weight.
[0162] Example 1
[0163] Substrate Overview: 0.5 mm thickness and composition B. Conditions Overview: First step IOX (30% KNO3 / 55% NaNO3 / 15% LiNO3), 420°C, for varying times. Analysis after first step IOX is provided in Table 1: Weight gain (grams and percentages), recorded FSM stress (CS max )(MPa), and the recorded FSM DOL(DOL FSM ) (μm). The absolute weight gain was taken as the average of the six weight differences before and after ion exchange, where the accuracy of a single measurement is limited by the balance to 0.0001 g. Therefore, the accuracy of the absolute weight gain was estimated to be 0.00006 g or 0.06 mg. The absolute weight gain (in mg) was divided by the total exposed area during the ion exchange process (both sides of the sample, in cm 2 ) to obtain the specific weight gain per unit area. For most samples of the present disclosure for which the specific weight gain per unit area is given, the pattern is a square with a side length of 5 cm, so the total exposed area on both sides is 50 cm 2 , since the thickness is usually 0.5mm, the negligible edge area is ignored. The precision of the specific weight gain per unit exposure area is evaluated to be 0.0012mg / cm 2 Thus, the fractional weight gain accuracy is approximately 0.002% for the 0.5 mm sample, 0.0025% for the 0.4 mm sample, and 0.0014% for the 0.7 mm sample. In the following table, the fractional weight gain values are rounded to the nearest 0.001%.
[0164] Table 1
[0165]
[0166]
[0167] The data in Table 1 show that the weight gain is limited to a small value that does not significantly exceed the weight gain contribution of K enrichment of the glass, so that any weight gain due to Na exchange for Li is negligible or negative. K enrichment is achieved without compromising the ability of the glass sample to obtain a stress profile with a high CT during a subsequent ion exchange step as a result of undesirable Na enrichment and Li depletion. Therefore, the specified bath of 420°C is optimized to achieve appropriate K enrichment of this glass to the desired depth. The surface CS does not change substantially with increasing K enrichment time, indicating lower stress relaxation at the specified temperature. K enrichment to a depth of more than 60 microns is confirmed as suggested by the FSM-DOL value.
[0168] Example 2
[0169] Various samples of Example 1 were further processed with a second step IOX. In general, the Example 2 samples progressed as follows: a first step IOX (30% KNO3 / 55% NaNO3 / 15% LiNO3) at 420°C for varying times; and a second step IOX (36% NaNO3 / 64% KNO3) at 380°C for 1.5 hours. The analysis after the second step IOX is provided in Table 2: The recorded FSM stress (CS max )(MPa), recorded FSM DOL(DOL FSM )(μm), surface stress (CS 表面 )(MPa), and SCALP CT(MPa).
[0170] Table 2
[0171]
[0172]
[0173] Table 2 demonstrates that the chemically enhanced process of the present invention comprising a K enrichment step in a properly designed bath achieves significant CS 拐点Increase (compare styles P14, P5, P2 and P9 with reference style A), while having similar surface CS and no significant loss of stress distribution area, manifested by CT values comparable to the reference style. Another valuable benefit is that the cumulative growth of the component due to ion exchange is significantly reduced compared to the reference, which is valuable for reducing the warpage and dimension specification temperature that occurs during the ion exchange process. The Li poisoning ratio of the Na-enriched bath is also reduced proportionally to the weight gain. In the examples herein, the poisoning of the bath having a weight ratio of NaNO3:KNO3 of 36:64 was reduced by about 20% as a result of the introduction of the K-enrichment step of the present invention.
[0174] Example 3
[0175] Various samples of Example 1 were further processed with a second step IOX. In general, the Example 3 samples progressed as follows: first step IOX at 420°C (30% KNO3 / 55% NaNO3 / 15% LiNO3) for varying times; and second step IOX at 380°C (49% NaNO3 / 51% KNO3) for varying times. The analysis after the second step IOX is provided in Table 3.1 (1.25 hour second step), Table 3.2 (1.5 hour second step), and Tables 3.3-3.4 (1.92 hour second step): Recorded FSM stress (CS max )(MPa), recorded FSM DOL(DOL FSM )(μm), surface stress (CS 表面 )(MPa), and SCALP CT(MPa).
[0176] Table 3.1
[0177]
[0178]
[0179] Similar to Table 2, Table 3.1 demonstrates how the process of the present invention achieves CS without significant loss of CS and CT. 拐点 , but this is an example bath with a higher NaNO3 / KNO3 weight ratio of 49 / 51, and the immersion time is 1.25 hours instead of 1.5 hours. The preferred partial equilibrium bath composition of the present invention achieves higher CS over a range of Na-enriched baths and diffusion times. 拐点 Likewise, in this embodiment, the poisoning ratio of the Na enrichment bath is also reduced by about 20%.
[0180] Table 3.2
[0181]
[0182]
[0183] Similar to Table 3.1, Table 3.2 demonstrates how the process of the present invention achieves CS without significant loss of CS and CT. 拐点 The Na enrichment time was 1.5 hours, which again demonstrated the benefit of the reduced poisoning rate of the Na enrichment bath.
[0184] Table 3.3
[0185]
[0186] Table 3.3 confirms that the process of the present invention provides CS 拐点 The results show a significant increase in the Na enrichment step and by extending the time in the Na enrichment step, a high CT can be achieved, very similar to the maximum CT of the reference process observed for REF C in Table 3.2. Despite the longer ion exchange time, there is still a benefit of reduced bath poisoning rate (e.g., weight gain of about 0.5% compared to 0.57% for REF C).
[0187] Table 3.4
[0188]
[0189] Example 4
[0190] The samples of Example 2 were further processed with a third step IOX. In summary, the Example 4 samples progressed as follows: first step IOX at 420°C (30% KNO3 / 55% NaNO3 / 15% LiNO3) for varying times; second step IOX at 380°C (36% NaNO3 / 64% KNO3) for 1.5 hours; and third step IOX at 370°C (9% NaNO3 / 91% KNO3 for 15 minutes). The analysis after the third step IOX is provided in Table 4-A: Recorded FSM stress (CS max )(MPa), recorded FSM DOL(DOL FSM )(μm), surface stress (CS 表面 )(MPa), CS 拐点 (MPa), and SCALP CT (MPa).
[0191] Table 4-A
[0192]
[0193]
[0194] Table 4-A demonstrates that when a high CS distribution is obtained, the K enrichment step of the present invention provides even greater CS 拐点 The increase was achieved by a final ion exchange step in a bath that was significantly enriched in KNO3 (a bath of 9% NaNO3 and 91% KNO3 provided good demonstration for the example glass composition, achieving a surface CS of about 800 MPa). Likewise, an increase in stress near the inflection point was observed without a significant decrease in CT, even with significant K enrichment depth (in one example over 60 microns). The benefit of reduced growth and therefore reduced ion exchange warpage was also demonstrated based on a decrease in total weight gain compared to the reference process, which was about 20%.
[0195] Example 5
[0196] The samples of Example 3 were further processed with a third step 10X. In general, the Example 5 samples progressed as follows: first step 10X (30% KNO3 / 55% NaNO3 / 15% LiNO3) at 420°C for varying times; second step 10X (49% NaNO3 / 51% KNO3) at 380°C for a recorded time; and third step 10X (9% NaNO3 / 91% KNO3, 370°C for 15 minutes) or (100% KNO3, 370°C for 12 minutes), as recorded. The analysis after the third step 10X is provided in Table 5.1 (1.25 hour second step and 9Na / 91K-15 minute third step), Table 5.2 (1.5 hour second step and 9Na / 91K-15 minute third step), Table 5.3 (1.92 hour second step and 9Na / 91K-15 minute third step) and Table 5.4 (1.92 hour second step and 100K-12 minute third step): Recorded FSM stress (CS max )(MPa), recorded FSM DOL(DOL FSM )(μm), surface stress (CS 表面 )(MPa), CS 拐点 (MPa), and SCALP CT (MPa).
[0197] Table 5.1
[0198]
[0199] Table 5.2
[0200]
[0201]
[0202] Table 5.3
[0203]
[0204] Similar to Table 4-A, Tables 5.1, 5.2 and 5.3 show that the process of the present invention can deliver higher CS than the reference process when CS is increased by the high KNO3 final step. 拐点 , this time in a process with a higher Na percentage in the Na enrichment step. At shorter Na enrichment times (e.g., 1.25 hours in Table 5.1), there may be a slightly more pronounced decrease in CT compared to the reference process that does not include a K enrichment step. Again, it is seen that an increase in the Na enrichment step time enables the inventive process to deliver a CS 拐点 Advancement without significant loss of CT, as demonstrated by the examples of Table 5.2 and especially Table 5.3).
[0205] Table 5.4
[0206]
[0207] Table 5.4 shows that even when the surface CS is maximized, there is still CS delivered by the process of the present invention. 拐点 This is achieved by immersing in a bath that provides only large alkaline ions (K ions) (in this case, a bath of only KNO3 without NaNO3). The high CS and CS k , without any noticeable loss of CT compared to the reference case not comprising a first K enrichment step.
[0208] Example 6: Analysis
[0209] Comparison of two IOX steps and different second IOX bath compositions. Figure 3 is the FSM layer depth (DOL) for two different second IOX step bath compositions FSM ) versus the first 10X step time (hours). Figure 3 The figure shows the DOL of Tables 2 and 3.2. FSM The data in the figure show that the longer the sample is left in the first step bath, the DOL FSM The figure also shows that the DOL in the 49%NaNO3 / 51%KNO3 bath is higher than that in the 36%NaNO3 / 64%KNO3 bath. FSM higher.
[0210] exist Figure 4 The FSM stress (CS) recorded in Tables 2 and 3.2 is shown in the figure. max). The data in the figure show that for all first step time points, the compressive stress at the surface measured by FSM after any of the second step bath conditions remains comparable. The figure also shows that the compressive stress at the surface of the 36% NaNO3 / 64% KNO3 bath is higher than that of the 49% NaNO3 / 51% KNO3 bath.
[0211] exist Figure 5 In the figure, the SCALP central tension (CT) of Tables 2 and 3.2 is shown. The data in the figure shows that the central tension of all samples in 49%NaNO3 / 51%KNO3 is higher than that in 36%NaNO3 / 64%KNO3 bath. There is an initial loss of CT of 5.2MPa compared to the reference sample and the 1.5 hour 1st step sample after the 49%NaNO3 / 51%KNO3 bath.
[0212] Comparison of three IOX steps and different second IOX bath compositions. Figure 6 is the FSM layer depth (DOL) for two different second IOX step bath compositions and containing the same third IOX step FSM ) versus the first 10X step time (hours). Figure 6 The figure shows the DOL of Tables 4 and 5.2. FSM The data in the figure show that the longer the sample is left in the first step bath, the greater the DOL recorded for the second and third step ion exchange. FSM The graph also shows that for the final first step time point of 67 hours, the 49% NaNO3 / 51 KNO3 bath recorded a higher DOL than the second step after 9% NaNO3 / 91% KNO3 FSM .
[0213] exist Figure 7 The FSM stress (CS) recorded in Tables 4 and 5.2 is shown in the figure. max ). The data in the figure shows the compressive stress at the surface measured by FSM, which shows an initial drop and then an increase for the 67 hour first step time point. The figure also shows that after the final step, for the 49% NaNO3 / 51% KNO3 bath, there is a higher compressive stress at the surface.
[0214] exist Figure 8 In the figure, the SCALP central tension (CT) of Tables 4 and 5.2 is shown. The data in the figure show that for the 49% NaNO3 / 51% KNO3 reference sample, the CT of the central tension initially drops, and slowly wins back the CT after the 67 hour first step time point.
[0215] Comparison of the second and third IOX steps. Fig. 9is the FSM layer depth (DOL) for the second IOX step bath and the third IOX step FSM ) versus the first 10X step time (hours). Fig. 9 The figure shows the DOL of Tables 3.2 and 5.2. FSM The data in the figure show that the longer the sample is left in the first step bath, the greater the DOL recorded for the second and third step ion exchange. FSM The figure also shows a lower DOL after 9% NaNO3 / 91% KNO3 compared to the second step bath. FSM .
[0216] exist Fig.10 The FSM stress (CS) recorded in Tables 3.2 and 5.2 is shown in the figure. max ). The data in the figure shows that for all first step time points, the compressive stress at the surface measured by FSM remains comparable after the 49% NaNO3 / 51% KNO3 second step bath condition. The figure also shows that after the 9% NaNO3 / 91% KNO3 final step, there is a higher compressive stress at the surface.
[0217] exist Fig.11 In the figure, the SCALP central tension (CT) of Tables 3.2 and 5.2 is shown. The data in the figure show that for the reference sample, the central tension after the final step decreased by 4MPa. For all time points after 1.5 hours, CT increased after the final step.
[0218] Fig.12 is the FSM layer depth (DOL) for the second IOX step bath and the third IOX step FSM ) versus the first 10X step time (hours). Fig.12 The figure shows the DOL of Tables 2 and 4. FSM The data in the figure show that the longer the sample is left in the first step bath, the greater the DOL recorded for the second and third step ion exchange. FSM The figure also shows that for the final time point of the first step IOX at 67 hours, the 9% NaNO3 / 91% KNO3 bath has a lower DOL than the second step bath. FSM .
[0219] exist Fig.13 The FSM stress (CS) recorded in Tables 2 and 4 is shown in the figure. max ). The data in the figure shows that for all first step time points, the compressive stress at the surface after the 36% NaNO3 / 64% KNO3 second step bath condition remains comparable. The figure also shows that after the 9% NaNO3 / 91% KNO3 final step, there is a higher compressive stress at the surface.
[0220] exist Fig.14 In the figure, the SCALP central tension (CT) of Tables 2 and 4 is shown. The data in the figure show that there is an increase in CT after the final step for all time points (including the reference sample).
[0221] Comparison of two IOX steps and different second IOX bath durations. Fig.15 is the FSM layer depth (DOL) for three different second IOX step bath durations FSM ) versus the first 10X step time (hours). Fig.15 The DOL of Tables 3.1, 3.2 and 3.3 are shown in Figure 3. FSM The data in the figure show that the longer the sample is left in the first step bath, the DOL FSM The figure also shows that for the sample in the 49% NaNO3 / 51% KNO3 bath for 1.5 hours, the DOL FSM For all Step IX time points, the DOL recorded FSM The trends are similar.
[0222] exist Fig.16 The FSM stresses (CS) recorded in Tables 3.1, 3.2 and 3.3 are shown in the figure. max The data in the figure show comparable compressive stresses measured by FSM for all different time points after the second step bath of 49% NaNO3 / 51% KNO3.
[0223] exist Fig.17 The SCALP central tension (CT) of Tables 3.1, 3.2 and 3.3 is shown in the figure. The data in the figure show that for all first step time points, the central tension of the 49% NaNO3 / 51% KNO3 second step bath after 1.92 hours is the highest.
[0224] Comparison of three IOX steps and different second IOX bath durations. Fig.18 is the FSM layer depth (DOL) for three different second IOX step bath durations and including the same third IOX step FSM ) versus the first 10X step time (hours). Fig.18 The DOL values of Tables 5.1, 5.2 and 5.3 are shown in Figure 5. FSM The data in the figure show that for all samples at different second step IX time points, the longer the sample is left in the first step bath, the DOL recorded after the third step ion exchange. FSMThe graph also shows that the sample at the 1.5 hour time point in the 49% NaNO3 / 51% KNO3 second bath recorded a higher DOL after the 9% NaNO3 / 91% KNO3 third step compared to the other time points. FSM .
[0225] exist Fig.19 The FSM stresses (CS) recorded in Tables 5.1, 5.2 and 5.3 are shown in Figure 5. max ). The data in the figure show comparable surface compressive stresses measured by FSM for all different time points after a second step bath of 49% NaNO3 / 51% KNO3 and then a final step of 9% NaNO3 / 91% KNO3. There is a decrease in CS for the first step time points of 15 hours and 30 hours after a 1.5 hour second step and at the 30 hour time point after a 1.92 hour second step. This may be due to the use of a wavelength of 590nm for the FSM 6000 protocol. It is to be understood that using, for example, a wavelength of 365nm, CS would show values more comparable to the reference sample.
[0226] exist Fig. 20 In the figure, the SCALP center tension (CT) of Tables 5.1, 5.2 and 5.3 is shown. The data in the figure shows that the second step bath of 49% NaNO3 / 51% KNO3 and then the final step of 9% NaNO3 / 91% KNO3 have comparable center tensions for all different time points. The data in the figure show that the center tension of the second step bath of 49% NaNO3 / 51% KNO3 after 1.92 hours is the highest for all first step time points except the 8 hour time point.
[0227] Comparison of the same two IOX steps. Fig.21 It is the SCALP central tension (CT) diagram of Tables 3.3 and 3.4.
[0228] Comparison of three IOX steps and different third IOX bath compositions and durations. Fig. 22 is the FSM layer depth (DOL) for the same second IOX step and a different third IOX step FSM ) versus the first 10X step time (hours). Fig. 22 The figure shows the DOL of Tables 5.3 and 5.4. FSM .
[0229] exist Fig.23 The FSM stresses (CS) recorded in Tables 5.3 and 5.4 are shown in the figure. max ).
[0230] exist Fig.24In the figure, the SCALP central tension (CT) of Tables 5.3 and 5.4 is shown.
[0231] Stress distribution. Fig.25A and 25B It is the stress distribution diagram of the sample according to Table 5.2. Fig.25A The graph shows the relationship between stress (MPa) and depth up to half the thickness of the article, and Fig.25B For product depths up to 110 microns. Fig.25A and 25B The stress distribution of is the smoothed distribution generated by RNF. The data in the figure show that the longer the ion exchange in the first step, the deeper the Na distribution at the surface.
[0232] Table 5.2.1-A provides: Depth of Peak Layer (DOL sp ), inflection point stress (CS 拐点 ), depth of compression (DOC), first average compressive stress in the stress intensification region (CS avg-1 ), depth of potassium layer (DOL K ), and the second average compressive stress (CS) in the potassium-rich region was determined and summarized. avg-2 ). DOL K Derived from the anti-WKB method and relative to Figure 30-31 The TM and TE refractive index distributions discussed. Table 5.2.1-B is the CS at specific depths. avg-1 Summary.
[0233] Table 5.2.1-A
[0234]
[0235] Table 5.2.1-B
[0236]
[0237]
[0238] Fig.26A and 26B It is the stress distribution diagram of the sample according to Table 4. Fig.26A The graph shows the relationship between stress (MPa) and depth up to half the thickness of the article, and Fig.26B For product depths up to 110 microns. Fig.26A and 26B The stress distribution of is the smoothed distribution generated by RNF. The data in the figure show that the longer the ion exchange in the first step, the deeper the Na distribution at the surface.
[0239] Table 4.1-A provides: Depth of the Spike Layer (DOL sp), inflection point stress (CS 拐点 ), depth of compression (DOC), first average compressive stress in the stress intensification region (CS avg-1 ), depth of potassium layer (DOL K ), and the second average compressive stress in the potassium-rich region (CS avg-2 ). DOL K Derived from the anti-WKB method and relative to Figure 30-31 The TM and TE refractive index distributions discussed. Table 4.1-B is the CS at specific depths. avg-1 Summary.
[0240] Table 4.1-A
[0241]
[0242]
[0243] Table 4.1-B
[0244]
[0245]
[0246] Fig. 27 It is the stress distribution diagram of the sample according to Table 5.1. Fig. 27 The graph shows stress (MPa) versus depth up to half the thickness of the article. Fig. 27 The stress distribution of is the smoothed distribution generated by RNF. The data in the figure show that the longer the ion exchange in the first step, the deeper the Na distribution at the surface.
[0247] Table 5.1.1-A provides: Depth of Peak Layer (DOL sp ), inflection point stress (CS 拐点 ), depth of compression (DOC), first average compressive stress in the stress intensification region (CS avg-1 ), depth of potassium layer (DOL K ), and the second average compressive stress in the potassium-rich region (CS avg-2 ). DOL K Derived from the anti-WKB method and relative to Figure 30-31 The TM and TE refractive index distributions discussed. Table 5.1.1-B is the CS at specific depths. avg-1 Summary.
[0248] Table 5.1.1-A
[0249]
[0250]
[0251] Table 5.1.1-B
[0252]
[0253]
[0254] Fig.28 It is the stress distribution diagram of the sample according to Table 5.3. Fig.28 The graph shows stress (MPa) versus depth up to half the thickness of the article. Fig.28 The stress distribution of is the smoothed distribution generated by RNF. The data in the figure show that the longer the ion exchange in the first step, the deeper the Na distribution at the surface.
[0255] Table 5.3.1-A provides: Depth of Peak Layer (DOL sp ), inflection point stress (CS 拐点 ), depth of compression (DOC), first average compressive stress in the stress intensification region (CS avg-1 ), depth of potassium layer (DOL K ), and the second average compressive stress (CS) in the potassium-rich region was determined and summarized. avg-2 ). DOL K Derived from the anti-WKB method and relative to Figure 30-31 The TM and TE refractive index distributions discussed. Table 5.3.1-B is the CS at specific depths. avg-1 Summary.
[0256] Table 5.3.1-A
[0257]
[0258] Table 5.3.1-B
[0259]
[0260] Tables 5.2.1-A, 4.1-A and 5.1.1-A confirm that: when the FSM or the compressive stress in the region of the peak depth of the characteristic depth of K enrichment full depth, DOL K A clear increase was obtained compared to the reference chemical fortification (Example REF C) which did not comprise a first step of K enrichment.
[0261] Tables 5.2.1-B, 4.1-B, and 5.1.1-B demonstrate that when the K enrichment step is long enough to provide this increase (e.g., 8 hours or longer K enrichment step), the peak depth DOL spThe average CS in the specific depth range of interest is significantly increased. During a drop event on certain hard surfaces with moderate roughness (e.g., rough granite), when the cover glass is locally bent, the flaws formed at impact depths most commonly below 60 microns (but sometimes as low as 15 microns) can lead to cracks. Increasing the average compressive stress in the region beyond the peak depth can help reduce the likelihood of such cracks, and these examples show such an increase. For depths below 20 microns, the increase in average CS is very large.
[0262] Compression depth. Fig.29 Graph showing Depth of Compression (DOC) versus First IOX Step Time (Hours) for the samples from Table 4. DOC was calculated from SCALP measurements using an SLP-1000 instrument. The data in the graph shows that the DOC decreases slightly the longer the sample is in the first step bath.
[0263] Figure 30-31 Partial stress distribution and TM and TE refractive index distributions obtained from sample P12 of Table 5.4 are shown, respectively, which sample received a third step of 100% KNO3 ion exchange at 380°C for 12 minutes, thereby advancing the surface compressive stress. Fig.30 The stress distribution is extracted up to an approximate K-enriched depth by the inverse WKB method, by measuring the effective refractive index of the optical mode bound to the K-enriched part of the distribution. The distribution is smoothed using a low-pass filter with a smoothing length of about 4.5 microns to reduce artifacts caused by the discrete nature of the measurement. The stress distribution is extracted almost to the entire K-enriched depth, which is based on Fig.31 Up to 75 microns is achieved. One of the refractive index profiles (in this case the TE profile) is extracted to a full depth of 75 microns because there are clearly bound optical modes whose effective refractive index is essentially at the same level as the substrate refractive index in the same TE polarization. Fig.31 An efficient way to determine the minimum depth of K penetration in a non-destructive manner is demonstrated: by measuring the depth of the TE and TM refractive index profiles by performing inverse WKB on carefully measured prism coupling spectra that are able to resolve the fringes corresponding to all boundary optical modes. Fig.30 A good non-destructive method was demonstrated to obtain partial stress distribution up to the K-enriched depth, including surface CS, and to characterize stress distribution and CS in the K-enriched region. 拐点 Has a pretty good estimate.
[0264] Example 7 - Prediction
[0265] In the embodiments discussed thus far, there is a reduction in compressive stress at depths beyond the maximum depth of targeted CS advancement provided by potassium enrichment, as well as a reduction in depth of compression (DOC), compared to a reference stress profile for consistent chemical strengthening in the absence of a potassium enrichment step. Such reductions in CS and DOC at large depths are generally highly undesirable, and as a result of the CS 拐点 (More generally, for embodiments of the present disclosure, in a DOL sp This was accepted as a compromise with a significant advance of the CS in the sub-area in the depth range between 40 μm.
[0266] The undesirable tradeoff can be partially or significantly mitigated by partial lithium enrichment of the interior of the glass during or after the potassium enrichment step. The lithium enrichment enables the presence of higher compressive stresses in deep regions that are K-poor but Na-rich after the final step of chemical strengthening. More specifically, lithium enrichment before the final step of introducing Na increases the gradient of Na concentration after the final step and thus achieves higher CS in regions where Na concentration is low due to K concentration (e.g., regions between the target CS advancement depth and the compression depth).
[0267] In some embodiments, lithium enrichment is performed simultaneously with K enrichment by employing a bath that is not in equilibrium with the glass for Li-Na exchange. More specifically, the mass fractions of KNO3, LiNO3, and NaNO3 in the bath are such that the glass receives a net increase in K and Li ions, and a net decrease in Na ions, and a weight loss is recorded as a result of this K and Li enrichment step, even though K ions are heavier than Na ions. In some embodiments, for a fixed KNO3 fraction, the ratio of LiNO3:NaNO3 increases compared to a bath that is in equilibrium for Li-Na exchange. In this example, the bath that is in equilibrium with the glass portion of composition B has: 30% KNO3: 15% LiNO3: 55% NaNO3, by weight. A bath that would accomplish both K and Li enrichment and yield a favorable balance between CS advancement in the target zone and CS loss in deeper zones would be a bath that is: 30% KNO3: 20% LiNO3: 50% NaNO3. The LiNO3:NaNO3 weight ratio in this bath is 0.4, which is higher than the 47% weight ratio in the partially balanced bath and promotes the Li enrichment of the glass of composition B. At the same time, the K enrichment concentration decreases slightly, but the CS in the final distribution 拐点The push should still be evident, with the currently disclosed range being above 160 MPa after one or two subsequent steps involving Na introduction in the same manner as in the previous embodiment. The CS loss from the maximum CS push depth to the depth of the DOC will be reduced, and the CT will be increased compared to the present embodiment. The final DOC may be slightly increased compared to the K enrichment case without Li enrichment, which is partly due to the lower concentration of K enrichment. In addition, after the Li enrichment step, slightly longer Na diffusion can be tolerated, which can partially recover the DOC loss over the partial DOC recovery associated with the slightly lower K enrichment concentration. For example, instead of 1.92 hours in the Na diffusion step (second step), the Na diffusion time at 380°C can be increased to 2-2.5 hours, and even to 3 hours in the case of more significant Li enrichment from the first step. In some cases, Li enrichment can cause changes in the effective diffusion coefficients of Na and K in subsequent steps, which may be beneficial for adjusting the Na diffusion time to achieve maximum stress in the distribution. The adjustment factor will typically be in the range of 2.
[0268] In some embodiments, the reduced K concentration incorporated into the glass as a result of the increase in the Li:Na ratio in the bath can be compensated by increasing the KNO3 content of the bath while subtracting more NaNO3 than LiNO3, thereby maintaining an elevated LiNO3:NaNO3 ratio. In an example, the K+Li enriched bath of the previous example can be changed to a ratio of 35% KNO3:18% LiNO3:47% NaNO3. This bath is expected to produce a similar increase in K enrichment as the original bath (30:15:55), but at the same time Li enriched and resulting in a higher CT distribution with higher integrated compressive stress over the compressive stress region. For the previous Li enriched example, the Na diffusion final step can benefit from a slight adjustment of the bath diffusion time or temperature to achieve a maximized integrated stress in the distribution.
[0269] In some embodiments, the Li enrichment step may be performed after the K enrichment step, particularly when a high content of LiNO3 in the bath (e.g., 30%, 40% or more) is advantageous. In this case, it may be undesirable to raise the bath temperature above 420°C, but it may be desirable to raise the bath temperature for K diffusion purposes, particularly for glasses where K diffusion is even slower than the glasses of the embodiments of composition B of the present disclosure. In an example, a first bath with a higher KNO3 content (e.g., 30%, 40%, 50%, or even 80%, 90%, or 95%) may be used in the first K enrichment step, with the remaining bath weight balanced between NaNO3 and LiNO3 to prevent significant changes in the composition inside the substrate or to make the substrate slightly Li-enriched. The main purpose of this step may be to quickly diffuse a large amount of K ions to greater depths via a higher K concentration in the bath combined with a hotter bath (if a heated bath is acceptable). Then, in a subsequent Li enrichment step, the bath has a higher content of LiNO3, a lower content of KNO3, and either a higher or lower NaNO3 than the first step bath. If the LiNO3 is significantly increased (e.g., to 20, 30, 40 or more bath wt %), the increase may also be advantageous for NaNO3, thereby avoiding significant strain and warping in the sample and difficulty maintaining the bath. This step may be performed at temperatures even below 420°C, thereby avoiding decomposition of LiNO3, if the bath composition has more than 40 wt % LiNO3. After such significant Li enrichment, after applying a Na enrichment final step similar to those described herein, samples with higher CS than presented in the examples to date in this disclosure may be produced. 拐点 and stress distribution of CT.
[0270] Example 8
[0271] The following examples use compositions C and D and substrates that are 0.7 mm thick by 50 mm by 50 mm. The stress profiles pursued in these examples seek to withstand cracking for particularly demanding applications involving cover glass for large and heavy articles that can generate very significant stresses after a drop event on a hard smooth or rough surface. The weight of the article is several times higher than that of a smartphone. Further improving CS 拐点 Of particular importance are considered glass compositions that have higher fracture toughness and stress distributions with greater DOC and greater total stress area (and associated greater CT).
[0272] A 0.7 mm thick sample of composition C was heat treated according to a thermal cycle commonly used for 3D forming, which resulted in a glass having a fictive temperature intermediate between the annealing point and the typical fusion-formed fictive temperature, corresponding to diffusion coefficients of K and Na ions intermediate between those of annealed glass and fusion-formed glass.
[0273] In the first K enrichment ion exchange step, the sample was immersed in a triple nitrate bath containing KNO3, LiNO3 and NaNO3 in a weight ratio of 58:19.4:22.6. The bath also had an additive of 0.5% silicic acid, based on the total weight of the nitrates, and an additive of 0.35% sodium nitrite (NaNO2), based on the total weight of the nitrates. The immersion time was 7 hours at 440°C. In the second Na enrichment step, the sample was immersed in a bath containing NaNO3 and KNO3 in a weight ratio of 25:75, at 400°C for 2.5 hours. In the third step, after immersion in a KNO3-only bath at 390°C for 20 minutes, a high CS spike was obtained on the surface. The resulting distribution of K ions penetrated more than 30 microns, and the CS 拐点 More than 400MPa.
[0274] This example shows that the method according to the invention is able to achieve CS in the region immediately after the peak not only in the composition according to composition B but also in other Li-containing glass compositions. 拐点 and CS, making chemical strengthening more suitable for higher CT and higher CS 拐点 . Characteristics Advance Average Compressive Stress CS avg-1 and CS avg-2 The apparent increase to 230 MPa and 164 MPa, respectively, is due to the combination of a favorable glass composition and a more aggressive K enrichment step that also provides some significant Li enrichment (as evidenced by the net weight loss during the K enrichment step). Table 6.1 provides the analysis of the 0.7 mm composition C sample.
[0275] Table 6.1
[0276]
[0277]
[0278] Composition D has a fracture toughness that is about 9% higher than composition C and about 15% higher than composition B, but has a significantly slower K diffusion coefficient and presents challenges in establishing deep K-rich regions and deep K spikes. Imparting a spike with maximum surface CS by performing a final ion exchange step in a bath that only provides K ions results in a lower CS at the base of the spike. 拐点 , which is also a shallow spike due to the lower K ion diffusion coefficient. Therefore, the boost and CS are provided in the region immediately after the spike.拐点 There is value in advancing, although this area may be shallower than in other embodiments.
[0279] A 0.7 mm thick sample of composition D was heat treated according to a thermal cycle commonly used for 3D forming, which resulted in a glass having a fictive temperature intermediate between the annealing point and the typical fusion forming fictive temperature, corresponding to a diffusion coefficient of K and Na ions intermediate between the diffusion coefficients of annealed and fusion formed glasses. In the two examples using composition D, the K enrichment step was obtained by immersion at 440°C for 8 hours in a bath containing KNO3, LiNO3 and NaNO3 in a weight ratio of 58:17:25, with the addition of 0.5% silicic acid, the immersion forming resulting in a K enrichment layer of about 300 MPa and a DOL of about 15 microns measured according to standard FSM-6000. The immersion also resulted in Li enrichment of the inner regions of the glass, as evidenced by a net weight loss of about 0.1% after this ion exchange step. The next step responsible for introducing a large amount of Na into the glass was carried out in a bath with a high content of NaNO3. In one embodiment, the bath contained a weight ratio of NaNO3:KNO3 of 40:60. In another example, the ratio was 28:72 and the glass specimen was immersed at 400°C. In both examples, the glass specimen was immersed at 430°C for 130 minutes. For both examples, the surface CS was advanced in a final ion exchange step, where the specimen was immersed in a bath of only KNO3 at 380°C for 20 minutes. Table 6.2 summarizes the resulting stress distribution and the main properties of the K-rich region.
[0280] Table 6.2
[0281]
[0282]
[0283] Implementation
[0284] Embodiment 1: A glass-based article comprising: a lithium-based aluminosilicate composition; a glass-based substrate having opposing first and second surfaces defining a substrate thickness (t), wherein t is less than or equal to 0.74 mm; and a stress profile comprising: a maximum compressive stress (CS) greater than or equal to 450 MPa; max ); a peak region extending from the first surface to the tail region; and a tail region extending to the center of the glass-based article; wherein the tail region comprises: a first average compressive stress (CS avg-1 ) greater than or equal to 100 MPa of the enhanced stress region; and a FSM layer depth (DOL) located at a depth greater than or equal to 13 microns FSM ).
[0285] Embodiment 2: The glass-based article of the preceding embodiment, wherein the first average compressive stress (CS avg-1 ) is less than or equal to 220MPa.
[0286] Embodiment 3: The glass-based article of any preceding embodiment, wherein the peak region extends to a depth of peak layer (DOL sp ), the tail region is from the peak layer depth (DOL sp ) starts to extend.
[0287] Embodiment 4: The glass-based article of any preceding embodiment, wherein the DOL sp Add 1 micron to DOL FSM Measuring CS avg-1 .
[0288] Embodiment 5: The glass-based article of any of the preceding embodiments, wherein the DOL sp Greater than or equal to 3 microns and less than or equal to 20 microns.
[0289] Embodiment 6: A glass-based article as described in any of the preceding embodiments, wherein CS is measured from a depth of 8 microns to a depth of 20 microns. avg-1 The range is greater than or equal to 125 to less than or equal to 195.
[0290] Embodiment 7: The glass-based article of embodiment 1, wherein CS is 0.0040 when measured from a depth of 10 microns to a depth of 30 microns. avg-1 The range is greater than or equal to 100 to less than or equal to 160.
[0291] Embodiment 8: The glass-based article of any preceding embodiment, wherein DOL FSM Located at a depth greater than or equal to 20 microns.
[0292] Embodiment 9: The glass-based article of the preceding embodiment, wherein the DOL FSM Located at a depth greater than or equal to 22 microns.
[0293] Embodiment 10: A glass-based article comprising: a lithium-based aluminosilicate composition; a glass-based substrate having opposing first and second surfaces defining a substrate thickness (t), wherein t is less than or equal to 0.74 mm; and a stress profile comprising: a maximum compressive stress (CS) greater than or equal to 450 MPa. max ); extending from the first surface to the peak layer depth (DOL sp ) peak area; and from DOL spA tail region extending to the center of the glass-based article; wherein the tail region includes: sp Add 1 micron to the depth of potassium layer (DOL K ) of a potassium-enriched region having a second average compressive stress (CS) greater than or equal to 100 MPa. avg-2 ), among which, DOL k Located at a depth greater than or equal to 20 microns.
[0294] Embodiment 11: The glass-based article of the preceding embodiment, wherein the average compressive stress (CS avg ) is less than or equal to 170MPa.
[0295] Embodiment 12: A glass-based article as in any one of Embodiments 10 to the preceding embodiments, wherein DOL K Located at a depth greater than or equal to 20 microns.
[0296] Embodiment 13: A glass-based article as in any one of Embodiments 10 to the preceding embodiments, wherein the inflection point compressive stress (CS k ) is greater than or equal to 100MPa.
[0297] Embodiment 14: A glass-based article as described in the previous embodiment, wherein CS 拐点 Greater than or equal to 160MPa.
[0298] Embodiment 15: A glass-based article as described in the preceding embodiment, wherein CS 拐点 Greater than or equal to 200MPa.
[0299] Embodiment 16: A glass-based article as in any one of embodiments 10 to the preceding embodiments, wherein DOL sp Greater than or equal to 3 microns.
[0300] Embodiment 17: The glass-based article of any preceding embodiment, wherein t is greater than or equal to 0.2 microns.
[0301] Embodiment 18: The glass-based article of any preceding embodiment, wherein the lithium aluminosilicate composition has a Na2O:Li2O molar ratio greater than or equal to 1.
[0302] Embodiment 19: The glass-based article of any preceding embodiment, wherein the maximum central tension (CT max ) is greater than or equal to 40MPa.
[0303] Embodiment 20: A glass-based article comprising: a lithium-based aluminosilicate composition, wherein the molar ratio of Na2O:Li2O in the lithium-based aluminosilicate composition is greater than or equal to 1; a glass-based substrate having first and second opposing surfaces defining a substrate thickness (t), wherein t is greater than or equal to 0.2 mm and less than or equal to 0.74 mm; and a stress profile comprising: a maximum compressive stress (CS) greater than or equal to 450 MPa. max ); Maximum central tension (CT) greater than or equal to 40MPa max ); a peak region extending from the first surface to the tail region; and a tail region extending to the center of the glass-based article; wherein the tail region comprises: a first average compressive stress (CS avg-1 ) greater than or equal to 100 MPa of the enhanced stress region; and a FSM layer depth (DOL) located at a depth greater than or equal to 13 microns FSM ).
[0304] Embodiment 21: A glass-based article as described in the previous embodiment, wherein the first average compressive stress (CS avg-1 ) is less than or equal to 220MPa.
[0305] Embodiment 22: The glass-based article of Embodiment 20, wherein CS is 0.0040 when measured from a depth of 8 microns to a depth of 20 microns. avg-1 The range is greater than or equal to 125 to less than or equal to 195.
[0306] Embodiment 23: The glass-based article of Embodiment 20, wherein CS is 0.0040 when measured from a depth of 10 microns to a depth of 30 microns. avg-1 The range is greater than or equal to 100 to less than or equal to 160.
[0307] Embodiment 24: The glass-based article of any preceding embodiment, wherein the depth of compression (DOC) is greater than or equal to 0.12t.
[0308] Embodiment 25: The glass-based article of any preceding embodiment, wherein CS max Greater than or equal to 600MPa.
[0309] Embodiment 26: A glass-based article as described in the preceding embodiment, wherein CS max Greater than or equal to 750MPa.
[0310] Embodiment 27: The glass-based article of any preceding embodiment, wherein the maximum central tension (CT max ) is greater than or equal to 55MPa.
[0311] Embodiment 28: A glass-based article as described in the preceding embodiment, wherein the maximum central tension (CT max ) is greater than or equal to 60MPa.
[0312] Embodiment 29: A glass-based article as described in the preceding embodiment, wherein the maximum central tension (CT max ) is greater than or equal to 65MPa.
[0313] Embodiment 30: A glass-based article as described in the preceding embodiment, wherein the maximum central tension (CT max ) is greater than or equal to 70MPa.
[0314] Embodiment 31: The glass-based article of any preceding embodiment, comprising a non-zero concentration of potassium oxide (K2O) from the first surface to a depth of potassium layer (DOL K ) is changing.
[0315] Embodiment 32: A glass-based article as described in any of Embodiments 10 to the preceding embodiments, wherein all points in the stress distribution in the peak region include a tangent with an absolute value of the slope of 20 MPa / micrometer or greater, and the stress distribution is located at a greater than DOL K All points in the deep tail region include tangents with absolute values of slopes less than 20 MPa / micrometer.
[0316] Embodiment 33: The glass-based article of any preceding embodiment, wherein the thickness is less than 0.70 mm.
[0317] Embodiment 34: A glass-based article comprising: a lithium-based aluminosilicate composition; a glass-based substrate having opposing first and second surfaces defining a substrate thickness (t), wherein t is greater than or equal to 0.2 mm and less than or equal to 0.74 mm; and a non-zero concentration of potassium oxide (KO) from the first surface to a depth of potassium layer (DOL). K ) is varied; and a stress distribution comprising: a maximum compressive stress (CS) greater than or equal to 450 MPa max ); Maximum central tension (CT) greater than or equal to 40MPa max ); extending from the first surface to the peak layer depth (DOL sp ) peak area; and from DOL sp A tail region extending to the center of the glass-based article; wherein the tail region includes: sp Add 1 micron extension to DOL KA potassium-enriched region having a second average compressive stress (CS) greater than or equal to 100 MPa and less than or equal to 170 MPa avg-2 ), among which, DOL k Located at a depth greater than or equal to 20 microns.
[0318] Embodiment 35: A consumer electronic product comprising: a housing having a front surface, a back surface, and side surfaces; electronic components at least partially located within the housing, the electronic components comprising at least a controller, a memory, and a display, the display being located on the front surface of the housing or adjacent to the front surface of the housing; and a cover arranged above the display, wherein at least a portion of at least one of the housing and the cover comprises a glass-based article of one of embodiments 1 to 34.
[0319] Embodiment 36: A method of making a glass-based article, comprising: exposing a glass-based substrate comprising sodium oxide and lithium oxide in a base composition to an ion exchange treatment to form a glass-based article, the glass-based substrate having opposing first and second surfaces defining a substrate thickness (t), the ion exchange treatment comprising: a first bath comprising a potassium salt, a sodium salt, and a lithium salt; and a second bath comprising a potassium salt, a sodium salt, and optionally a lithium salt; wherein t is less than or equal to 0.74 mm and the substrate comprises a composition wherein the molar ratio of Na2O:Li2O in the lithium-based aluminosilicate composition is greater than or equal to 1; wherein the glass-based article comprises a stress profile comprising: a maximum compressive stress (CS) greater than or equal to 450 MPa max ); extending from the first surface to the peak layer depth (DOL sp ) peak area; and from DOL sp A tail region extending to the center of the glass-based article; wherein the tail region includes: sp Add 1 micron to the depth of potassium layer (DOL K ) of a potassium-enriched region having a second average compressive stress (CS) greater than or equal to 100 MPa. avg-2 ), among which, DOL K Located at a depth greater than or equal to 20 microns.
[0320] Embodiment 37: A method as described in Embodiment 36, wherein, in the first bath, the potassium salt is KNO3, present in an amount greater than or equal to 30 weight percent; the sodium salt is NaNO3; the lithium salt is LiNO3; and the weight ratio of LiNO3:NaNO3 in the first bath is 0.273±0.1% to 0.858±0.1%.
[0321] Embodiment 38: A method as described in Embodiment 36 or 37, wherein after exposure to the first bath, the glass-based substrate has a weight gain value of greater than or equal to -0.3 wt.% to less than or equal to 0.1 (1 + 0.02 / t)%, where t is measured in millimeters.
[0322] Embodiment 39: The method of one of Embodiments 36 to 38, wherein the ion exchange treatment further comprises a third bath comprising a potassium salt and a sodium salt, wherein the potassium salt content in the third bath is greater than or equal to 90 wt%.
[0323] Embodiment 40: A method as described in one of embodiments 36 to 39, wherein the first bath comprises: 20-60 wt.% NaNO3, 10-20 wt.% LiNO3 and 25-60 wt.% KNO3, wherein the content of NaNO3, LiNO3 and KNO3 totals 100%, and the glass substrate includes a basic composition with a molar ratio of Na2O:Li2O greater than or equal to 1.
[0324] Embodiment 41: A method as described in embodiment 40, wherein the first bath contains: 50-60 wt.% NaNO3, 10-20 wt.% LiNO3 and 25-35 wt.% KNO3, wherein the total content of NaNO3, LiNO3 and KNO3 is 100%, and the glass substrate includes a basic composition with a molar ratio of Na2O:Li2O greater than or equal to 1.3.
[0325] Embodiment 42: A method as described in embodiment 40, wherein the first bath contains: 20-30 wt.% NaNO3, 10-20 wt.% LiNO3 and 55-60 wt.% KNO3, wherein the total content of NaNO3, LiNO3 and KNO3 is 100%, and the glass substrate includes a basic composition with a molar ratio of Na2O:Li2O greater than or equal to 1 and less than or equal to 1.3.
[0326] Although the above content relates to various embodiments, other and further embodiments of the present disclosure may be designed without departing from the basic scope, and the scope of the present disclosure is determined by the appended claims. The features of the present disclosure may be arbitrarily and fully combined, for example as described in the following embodiments.
[0327] Directional terms used herein, such as up, down, left, right, front, back, top, bottom, inside, and outside, are only used with reference to the drawings and are not intended to represent absolute orientations.
[0328] As used herein, the terms "the," "a," or "an" mean "at least one," and should not be limited to "only one," unless clearly indicated to the contrary. Thus, for example, reference to "a component" includes embodiments having two or more such components, unless the context clearly indicates otherwise.
[0329] As used herein, unless otherwise indicated, the terms "comprises" and "includes" and variations thereof should be understood as synonymous and open ended. A list of elements following the transitional term comprises or includes is a non-exclusive example, such that there may be elements other than those specifically listed.
[0330] It is obvious to those skilled in the art that various modifications and variations can be made to the present disclosure without departing from the scope and spirit of the present disclosure. Therefore, the present disclosure is intended to cover such modifications and variations.
Claims
1. A glass-based article comprising: Lithium-based aluminosilicate compositions; a glass-based substrate having opposing first and second surfaces defining a substrate thickness (t), wherein t is less than or equal to 0.74 mm; and Stress distribution, which includes: Maximum compressive stress (CS) greater than or equal to 450 MPa max ); a peak region extending from the first surface to the tail region; and a tail region extending to the center of the glass-based article; The tail area includes: Having a first average compressive stress (CS) greater than or equal to 100 MPa avg-1 ) of the enhanced stress region; and The depth of the FSM layer (DOL) at a depth greater than or equal to 13 microns FSM ).
2. The glass-based article of claim 1, wherein: The first average compressive stress (CS avg-1 ) is less than or equal to 220MPa.
3. The glass-based article of claim 1, wherein: The spike region extends to the depth of the spike layer (DOL sp ), the tail region is from the peak layer depth (DOL sp ) starts to extend.
4. The glass-based article of claim 1, wherein: From DOL sp Add 1 micron to DOL FSM Measuring CS avg-1 .
5. The glass-based article of claim 1, wherein: DOL sp Greater than or equal to 3 microns and less than or equal to 20 microns.
6. The glass-based article of claim 1, wherein: When measured from 8 μm to 20 μm depth, CS avg-1 The range is greater than or equal to 125 to less than or equal to 195.
7. The glass-based article of claim 1, wherein: When measured from 10 μm to 30 μm depth, CS avg-1 The range is greater than or equal to 100 to less than or equal to 160.
8. The glass-based article of any one of claims 1-7, wherein: t is greater than or equal to 0.2 mm.
9. The glass-based article of any one of claims 1-7, wherein: The molar ratio of Na2O:Li2O in the lithium-based aluminosilicate composition is greater than or equal to 1.
10. The glass-based article of any one of claims 1-7, wherein: Maximum central tension (CT max ) is greater than or equal to 40MPa.
11. The glass-based article of any one of claims 1-7, wherein: The depth of compression (DOC) is greater than or equal to 0.12t.
12. The glass-based article of any one of claims 1-7, wherein: CS max Greater than or equal to 750MPa.
13. The glass-based article of any one of claims 1-7, wherein: Maximum central tension (CT max ) is greater than or equal to 70MPa.
14. A glass-based article comprising: Lithium-based aluminosilicate compositions; a glass-based substrate having opposing first and second surfaces defining a substrate thickness (t), wherein t is greater than or equal to 0.2 mm and less than or equal to 0.74 mm; A potassium oxide (K2O) having a non-zero concentration from the first surface to a depth of potassium layer (DOL K ) is variable; and Stress distribution, which includes: Maximum compressive stress (CS) greater than or equal to 450 MPa max ); Maximum central tension (CT) greater than or equal to 40MPa max ); From the first surface to the peak layer depth (DOL sp ) peak area; and From DOL sp a tail region extending to the center of the glass-based article; The tail area includes: From DOL sp Add 1 micron extension to DOL K A potassium-enriched region having a second average compressive stress (CS) greater than or equal to 100 MPa and less than or equal to 170 MPa avg-2 ); Among them, DOL K Located at a depth of greater than or equal to 20 microns.
15. A consumer electronic product comprising: a housing having a front surface, a back surface, and side surfaces; an electronic assembly at least partially located within the housing, the electronic assembly including at least a controller, a memory, and a display, the display being located at or adjacent to the front surface of the housing; as well as an overlay disposed on the display; wherein at least a portion of at least one of the housing and the cover comprises the glass-based article of any one of claims 1-7.
16. A method of making a glass-based article, comprising: Exposing a glass-based substrate having a base composition comprising sodium oxide and lithium oxide to an ion exchange treatment to form a glass-based article, the glass-based substrate having opposing first and second surfaces defining a substrate thickness (t), the ion exchange treatment comprising: a first bath comprising potassium and sodium and lithium salts; and a second bath comprising a potassium salt, a sodium salt, and optionally a lithium salt; wherein t is less than or equal to 0.74 mm and the substrate comprises the following composition, wherein the molar ratio of Na2O:Li2O in the lithium-based aluminosilicate composition is greater than or equal to 1; Wherein, the glass-based product comprises the following stress distribution, which comprises: Maximum compressive stress (CS) greater than or equal to 450 MPa max ); From the first surface to the peak layer depth (DOL sp ) peak area; and From DOL sp a tail region extending to the center of the glass-based article; The tail area includes: From DOL sp Add 1 micron to the depth of potassium layer (DOL K ) of a potassium-enriched region having a second average compressive stress (CS) greater than or equal to 100 MPa. avg-2 ); Among them, DOL K Located at a depth of greater than or equal to 20 microns.
17. The method of claim 16, wherein: In the first bath, the potassium salt is KNO3, present in an amount greater than or equal to 30 wt%; the sodium salt is NaNO3; the lithium salt is LiNO3; and the weight ratio of LiNO3:NaNO3 in the first bath is 0.273±0.1% to 0.858±0.1%.
18. The method of claim 16, wherein: After exposure to the first bath, the glass-based substrate has a percent weight gain value of greater than or equal to -0.3% to less than or equal to 0.1 (1 + 0.02 / t)%, where t is measured in millimeters.
19. The method according to any one of claims 16 to 18, wherein: The ion exchange treatment further includes a third bath comprising a potassium salt and a sodium salt, wherein the potassium salt content in the third bath is greater than or equal to 90 weight percent.
20. The method of any one of claims 16 to 18, wherein: The first bath comprises: 20-60 wt % NaNO3, 10-20 wt % LiNO3 and 25-60 wt % KNO3, wherein the contents of NaNO3, LiNO3 and KNO3 total 100%, and the glass substrate comprises a base composition with a molar ratio of Na2O:Li2O greater than or equal to 1.
Citation Information
Patent Citations
Ion-exchangeable mixed alkali aluminosilicate glasses
US10906834B2
Glasses with low excess modifier content
US20190161390A1
Glass-based articles with improved stress profiles
US20200002225A1
Systems and methods for measuring a profile characteristic of a glass sample
US8854623B2
Glass-based articles including a stress profile comprising two regions, and methods of making
CN107265884A